Resin composition, pellet, and molded article
Patent Information
- Application Number
- JP2023130436
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-21
Smart Images

Figure 2025025569000001 
Figure 2025025569000002 
Figure 2025025569000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a pellet, and a molded article. [Background technology]
[0002] 2. Description of the Related Art Conventionally, resin compositions containing a polyalkylene terephthalate resin, such as a polybutylene terephthalate resin, and a polycarbonate resin have been investigated (for example, Patent Document 1). Such resin compositions are widely used in electrical and electronic equipment parts, interior and exterior automotive parts, other electrical equipment parts, machine parts, and the like. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2021 / 186025 Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, from the viewpoint of reducing the environmental impact, the use of recycled products as thermoplastic resins has been considered. However, when recycled thermoplastic resins are used, various physical properties of the molded products obtained tend to be inferior. In the present invention, an attempt was made to use recycled polycarbonate resin under such circumstances. Specifically, the present invention aims to provide a resin composition containing a polyalkylene terephthalate resin, a recycled polycarbonate resin, and a flame retardant, which is capable of achieving physical properties comparable to those of virgin polycarbonate resin or better than those of virgin polycarbonate resin alone, as well as pellets and molded articles. [Means for solving the problem]
[0005] In view of the above problems, the present inventors have conducted research and found that the above problems can be solved by using a specific polycarbonate resin as a recycled polycarbonate resin and blending a flame retardant and an elastomer therein. Specifically, the above problems were solved by the following means. <1> The composition contains 3 to 30 parts by mass of an elastomer and 5 to 50 parts by mass of a flame retardant relative to 100 parts by mass of a total of a polyalkylene terephthalate resin and a polycarbonate resin, the mass ratio of the polyalkylene terephthalate resin to the polycarbonate resin in the total of 100 parts by mass of the polyalkylene terephthalate resin and the polycarbonate resin is 80 / 20 to 20 / 80, the polycarbonate resin contains a recycled polycarbonate resin, and the melt volume rate (MVR) of the recycled polycarbonate resin measured according to ISO1133 under conditions of 300°C and a load of 1.20 kgf is 2 to 11 cm. 3 / 10 minutes and a branching amount of 50 to 3500 ppm by mass. <2> A mass ratio of the polyalkylene terephthalate resin to the polycarbonate resin in a total of 100 parts by mass of the polyalkylene terephthalate resin and the polycarbonate resin is 30 / 70 to 55 / 45. <1> The resin composition according to claim 1. <3> The recycled polycarbonate resin comprises a polycarbonate resin derived from a bottle and / or a sheet; <1> or <2> The resin composition according to claim 1. <4> Further, the composition contains an ester exchange inhibitor in an amount of 0.01 to 2 parts by mass per 100 parts by mass of the polyalkylene terephthalate resin and the polycarbonate resin in total. <1> ~ <3> 10. The resin composition according to claim 9 . <5> The polyalkylene terephthalate resin includes a polybutylene terephthalate resin. <1> ~ <4> 10. The resin composition according to claim 9 . <6> a mass ratio of the polyalkylene terephthalate resin to the polycarbonate resin in a total of 100 parts by mass of the polyalkylene terephthalate resin and the polycarbonate resin is 30 / 70 to 55 / 45, the recycled polycarbonate resin contains a polycarbonate resin derived from a bottle and / or a sheet, and further contains an ester exchange inhibitor in an amount of 0.01 to 2 parts by mass relative to a total of 100 parts by mass of the polyalkylene terephthalate resin and the polycarbonate resin, and the polyalkylene terephthalate resin contains a polybutylene terephthalate resin, <1> ~ <5> 10. The resin composition according to claim 9 . <7> <1> ~ <6> 2. A pellet of the resin composition according to claim 1. <8> <1> ~ <6> 2. A molded article formed from the resin composition according to claim 1. <9> <7> A molded article formed from the pellets according to claim 1. Effect of the Invention
[0006] According to the present invention, it is possible to provide a resin composition containing a polyalkylene terephthalate resin, a recycled polycarbonate resin, and a flame retardant, which is capable of achieving physical properties comparable to those achieved when virgin polycarbonate resin is used or better than those achieved when only virgin polycarbonate resin is used, as well as pellets and molded articles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values are those at 23° C. unless otherwise specified. If the measurement methods, etc. described in the standards shown in this specification vary from year to year, they will be based on the standards as of January 1, 2023, unless otherwise stated.
[0008] The resin composition of the present embodiment contains 3 to 30 parts by mass of an elastomer and 5 to 50 parts by mass of a flame retardant relative to 100 parts by mass of a total of a polyalkylene terephthalate resin and a polycarbonate resin, the mass ratio of the polyalkylene terephthalate resin to the polycarbonate resin in the total 100 parts by mass of the polyalkylene terephthalate resin and the polycarbonate resin is 80 / 20 to 20 / 80, the polycarbonate resin contains a recycled polycarbonate resin (recycled polycarbonate resin), and the melt volume rate (MVR) of the recycled polycarbonate resin measured according to ISO1133 under conditions of 300°C and a load of 1.20 kgf is 2 to 11 cm. 3 / 10 minutes and the branching amount is 50 to 3500 ppm by mass. By adopting such a configuration, a resin composition containing a polyalkylene terephthalate resin, a recycled polycarbonate resin, and a flame retardant can be obtained, which is capable of achieving physical properties comparable to those achieved when virgin polycarbonate resin is used, or better than those achieved when only virgin polycarbonate resin is used. For example, when a flame retardant is blended into a resin composition, the impact resistance usually tends to be poor, but in this embodiment, by using a specific recycled polycarbonate resin, high impact resistance tends to be achieved. In addition, the resin composition of this embodiment also tends to maintain high flame retardancy. Furthermore, when recycled polycarbonate resin is used, the nominal strain at break tends to be poor. In this embodiment, by using a specific recycled polycarbonate resin, the nominal strain at break tends to be improved. In addition, the resin composition of this embodiment tends to be able to increase the crystallization temperature (Tc).
[0009] <Polyalkylene terephthalate resin> The resin composition of the present embodiment contains a polyalkylene terephthalate resin. The polyalkylene terephthalate resin is a polyester obtained by, for example, polycondensation of terephthalic acid as a dicarboxylic acid compound and a diol, and may be either a homopolyester or a copolyester.
[0010] As the dicarboxylic acid compound constituting the polyalkylene terephthalate resin, a terphthalic acid compound or an ester-forming derivative thereof is preferably used. Aromatic dicarboxylic acids other than terephthalic acid can also be used in combination. Examples of such dicarboxylic acids include isophthalic acid, orthophthalic acid, 1,5-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, biphenyl-2,2'-dicarboxylic acid, biphenyl-3,3'-dicarboxylic acid, biphenyl-4,4'-dicarboxylic acid, diphenylether-4,4'-dicarboxylic acid, diphenylmethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, diphenylisopropylidene-4,4'-dicarboxylic acid, 1,2-bis(phenoxy)ethane-4,4'-dicarboxylic acid, anthracene-2,5-dicarboxylic acid, anthracene-2,6-dicarboxylic acid, p-tert-phenylene-4,4'-dicarboxylic acid, and pyridine-2,5-dicarboxylic acid. These can be used in the polycondensation reaction as ester-forming derivatives such as dimethyl esters in addition to free acids. Of the above, isophthalic acid or its ester-forming derivatives are particularly preferred.
[0011] In addition, one or more aliphatic dicarboxylic acids such as adipic acid, azelaic acid, dodecanedioic acid, and sebacic acid, and alicyclic dicarboxylic acids such as 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid can be mixed and used in small amounts together with terephthalic acid and the above-mentioned aromatic dicarboxylic acids.
[0012] Examples of dihydroxy compounds constituting the polyalkylene terephthalate resin include aliphatic diols such as ethylene glycol, propylene glycol, butanediol, hexylene glycol, neopentyl glycol, 2-methylpropane-1,3-diol, diethylene glycol, and triethylene glycol, alicyclic diols such as cyclohexane-1,4-dimethanol, and mixtures thereof. Among these, butanediol and ethylene glycol are particularly preferred.
[0013] In addition, one or more long-chain diols having a molecular weight of 400 to 6,000, such as polyethylene glycol, poly-1,3-propylene glycol, polytetramethylene glycol, etc. may be copolymerized. In addition, aromatic diols such as hydroquinone, resorcinol, naphthalene diol, dihydroxydiphenyl ether, and 2,2-bis(4-hydroxyphenyl)propane may also be used.
[0014] In addition to the above-mentioned bifunctional monomers, a small amount of a trifunctional monomer such as trimellitic acid, trimesic acid, pyromellitic acid, pentaerythritol, or trimethylolpropane may be used in combination to introduce a branched structure, or a monofunctional compound such as a fatty acid may be used in combination to adjust the molecular weight.
[0015] The polyalkylene terephthalate resin is preferably one that is mainly composed of polycondensation of terephthalic acid and diol, i.e., one that is composed of this polycondensate in an amount of more than 50% by mass of the entire resin, preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, still more preferably 95% by mass or more, and even more preferably 99% by mass or more. The diol is preferably an aliphatic diol, more preferably 1,4-butanediol and / or ethylene glycol, and more preferably 1,4-butanediol.
[0016] The amount of terminal carboxyl groups of the polyalkylene terephthalate resin (preferably polybutylene terephthalate resin) may be appropriately selected and determined, but is usually 60 eq / ton or less, preferably 50 eq / ton or less, and more preferably 30 eq / ton or less. By making it 60 eq / ton or less, gas generation during melt molding of the resin composition tends to be more effectively suppressed. The lower limit of the amount of terminal carboxyl groups is not particularly set, but is usually 3 eq / ton or more, preferably 5 eq / ton or more, and more preferably 10 eq / ton or more.
[0017] The amount of terminal carboxyl groups in the polyalkylene terephthalate resin is a value measured by dissolving 0.5 g of the resin in 25 mL of benzyl alcohol and titrating it with a 0.01 mol / L benzyl alcohol solution of sodium hydroxide. The amount of terminal carboxyl groups can be adjusted by any conventional method, such as adjusting the polymerization conditions such as the raw material charge ratio during polymerization, the polymerization temperature, and the pressure reduction method, or by reacting a terminal blocking agent.
[0018] The intrinsic viscosity of the polyalkylene terephthalate resin (preferably polybutylene terephthalate resin) is preferably 0.65 dL / g or more, more preferably 0.80 dL / g or more, even more preferably 1.00 dL / g or more, even more preferably 1.20 dL / g or more, and even more preferably 1.23 dL / g or more. By making it equal to or more than the lower limit, there is a tendency to improve the impact resistance and the nominal breaking strain. In addition, the intrinsic viscosity of the polyalkylene terephthalate resin (preferably polybutylene terephthalate resin) is preferably 1.50 dL / g or less, more preferably 1.40 dL / g or less, even more preferably 1.35 dL / g or less, and even more preferably 1.30 dL / g or less. By making it equal to or less than the upper limit, there is a tendency to suppress the decrease in the fluidity of the resin during injection molding, and there is a tendency to suppress the peak pressure during injection molding.
[0019] The intrinsic viscosity is measured by the following method. Polyalkylene terephthalate resin pellets are dissolved in a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (mass ratio 1 / 1) by stirring at 110°C for 1 hour to a concentration of 1.00 g / dL. The solution is then cooled to 30°C. The time it takes for the sample solution and the solvent alone to fall at 30°C is measured using a fully automatic solution viscometer, and the intrinsic viscosity is calculated using the formula: Intrinsic viscosity=((1+4K H η sp ) 0.5 -1) / (2K H C) Here, η sp = η / η0-1, where η is the time it takes for the sample solution to fall, η0 is the time it takes for the solvent alone to fall, C is the concentration of the sample solution (g / dL), and K H is Huggins' constant. K H was set to 0.33. The fully automatic solution viscometer used is a product of Shibayama Scientific Co., Ltd. When the resin composition of the present embodiment contains two or more types of polyalkylene terephthalate resins, the intrinsic viscosity is the intrinsic viscosity of the mixture.
[0020] The preferred polyalkylene terephthalate resin is one in which 95 mol % or more of the acid component is terephthalic acid and 95 mol % or more of the alcohol component is an aliphatic diol, and representative examples thereof are polybutylene terephthalate resin and polyethylene terephthalate resin. These are preferably close to homopolyesters, that is, 95 mol % or more of the entire resin is composed of terephthalic acid components and 1,4-butanediol or ethylene glycol components. The polyalkylene terephthalate resin is preferably a polybutylene terephthalate resin and / or a polyethylene terephthalate resin. Among them, the polyalkylene terephthalate resin preferably contains polybutylene terephthalate resin as a main component, and more than 50% by mass of the polyalkylene terephthalate resin is preferably polybutylene terephthalate resin. In this case, it is also preferable that the content of polyethylene terephthalate resin is less than 50% by mass.
[0021] Polybutylene terephthalate resin can be produced by batch or continuous melt polymerization of a dicarboxylic acid component mainly composed of terephthalic acid or an ester derivative thereof and a diol component mainly composed of 1,4-butanediol. After producing a low molecular weight polybutylene terephthalate resin by melt polymerization, the degree of polymerization (or molecular weight) can be increased to a desired value by further solid-phase polymerization under a nitrogen stream or reduced pressure.
[0022] The polybutylene terephthalate resin is preferably produced by a continuous melt polycondensation process of a dicarboxylic acid component mainly composed of terephthalic acid and a diol component mainly composed of 1,4-butanediol.
[0023] The catalyst used in carrying out the esterification reaction may be a conventionally known catalyst, and examples thereof include titanium compounds, tin compounds, magnesium compounds, calcium compounds, etc. Among these, titanium compounds are particularly preferred. Specific examples of titanium compounds as esterification catalysts include titanium alcoholates such as tetramethyl titanate, tetraisopropyl titanate, and tetrabutyl titanate, and titanium phenolates such as tetraphenyl titanate.
[0024] The polybutylene terephthalate resin may be a polybutylene terephthalate resin modified by copolymerization (hereinafter, also referred to as a "modified polybutylene terephthalate resin"), and specific preferred copolymers include polyester ether resins copolymerized with polyalkylene glycols (particularly polytetramethylene glycol), dimer acid copolymerized polybutylene terephthalate resins, and isophthalic acid copolymerized polybutylene terephthalate resins.
[0025] When a polyester ether resin copolymerized with polytetramethylene glycol is used as the modified polybutylene terephthalate resin, the proportion of the tetramethylene glycol component in the copolymer is preferably 3 to 40 mass%, more preferably 5 to 30 mass%, and even more preferably 10 to 25 mass%. When a dimer acid copolymerized polybutylene terephthalate resin is used as the modified polybutylene terephthalate resin, the proportion of the dimer acid component in the total carboxylic acid components is preferably 0.5 to 30 mol %, more preferably 1 to 20 mol %, and even more preferably 3 to 15 mol %, in terms of carboxylic acid groups. When an isophthalic acid copolymerized polybutylene terephthalate resin is used as the modified polybutylene terephthalate resin, the proportion of isophthalic acid components in all carboxylic acid components is preferably 1 to 30 mol %, more preferably 1 to 20 mol %, and even more preferably 3 to 15 mol %, in terms of carboxylic acid groups. Among the modified polybutylene terephthalate resins, polyester ether resins copolymerized with polytetramethylene glycol and isophthalic acid copolymerized polybutylene terephthalate resins are preferred.
[0026] The content of the polyalkylene terephthalate resin (preferably polybutylene terephthalate resin) in the resin composition of this embodiment is preferably 10 mass% or more, more preferably 20 mass% or more, and even more preferably 30 mass% or more, based on 100 mass% of the resin composition, and is preferably 60 mass% or less, and more preferably 50 mass% or less. The resin composition of the present embodiment may contain only one type of polyalkylene terephthalate resin (preferably polybutylene terephthalate resin), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.
[0027] <Polycarbonate resin> The resin composition of the present embodiment contains a polycarbonate resin. Polycarbonate resin is a homopolymer or copolymer obtained by reacting a dihydroxy compound or a small amount of a polyhydroxy compound with phosgene or a carbonic acid diester. The method for producing the polycarbonate resin is not particularly limited, and polycarbonate resins produced by the conventionally known phosgene method (interfacial polymerization method) or melting method (ester exchange method) can be used. By using a polycarbonate resin obtained by the melting method, the polycarbonate resin tends to have a branched structure more easily. Also, in the interfacial polymerization method, a branching agent can be used during polymerization of the polycarbonate resin to obtain a polycarbonate resin having a branched structure.
[0028] The dihydroxy compound as the raw material is preferably an aromatic dihydroxy compound, more preferably bisphenol, and even more preferably bisphenol A. In addition, a compound in which one or more tetraalkylphosphonium sulfonates are bonded to the above aromatic dihydroxy compound can also be used.
[0029] In this embodiment, it is preferable that 90% by mass or more of the dihydroxy compound, which is the raw material monomer, is a polycarbonate resin derived from bisphenol A, and more preferably 95% by mass or more of the polycarbonate resin derived from bisphenol A. The constitutional units represented by the formulas (C1) to (C4) described later are also derived from bisphenol A, and are produced, for example, when polycarbonate is polymerized (melt method) by transesterification of bisphenol A and diphenyl carbonate, by a transition reaction (Fries transition) occurring in the polymerization reaction system. The constitutional units represented by the formulas (C1) to (C4) described later are also produced by the Fries transition of the polycarbonate resin derived from bisphenol A due to photodegradation caused by ultraviolet rays or the like. Two or more kinds of polycarbonate resins may be mixed and used.
[0030] In order to adjust the molecular weight of the polycarbonate resin, a monovalent aromatic hydroxy compound may be used, such as m- and p-methylphenol, m- and p-propylphenol, p-tert-butylphenol, and p-long-chain alkyl-substituted phenol.
[0031] The polycarbonate resin used in the present embodiment includes a polycarbonate resin derived from recycling (recycled polycarbonate resin). Examples of recycled polycarbonate resins include those obtained by material recycling in which recovered used polycarbonate resin moldings are crushed, washed, and reused, and those obtained by chemical recycling (chemical decomposition method), and those obtained by material recycling are preferred. Chemical recycling involves chemically decomposing the collected used polycarbonate resin molded bodies and returning them to the raw material level to resynthesize polycarbonate resin, while material recycling involves, for example, removing foreign matter from the collected used polycarbonate resin molded bodies, pulverizing them, washing them with an alkali, drying them, and pulverizing them into flakes or pelletizing them with an extruder. In addition, polycarbonate resin that is not a recycled polycarbonate resin is called virgin polycarbonate resin.
[0032] Examples of recycled polycarbonate resins include polycarbonate resins derived from bottles, polycarbonate resins derived from discs, sheets (including polycarbonate resins derived from films), polycarbonate resins derived from meter covers (e.g., power meter covers), and polycarbonate resins derived from headlamp lenses; at least one of polycarbonate resins derived from bottles, polycarbonate resins derived from meter covers, and polycarbonate resins derived from headlamp lenses is preferred, and polycarbonate resins derived from bottles and / or sheets are more preferred.
[0033] Examples of recycled polycarbonate resins include post-consumer recycled (PCR) products, which are made by collecting and recycling used products on the market, and post-industrial recycled (PIR) products, which are made by recycling materials generated in the manufacturing process of products before they are released on the market. Either type is acceptable, but from the viewpoint of reducing the environmental burden, post-consumer recycled products are preferred.
[0034] The recycled polycarbonate resin used in this embodiment preferably contains 10 to 80 ppm by mass of bisphenol A. The content of bisphenol A in the recycled polycarbonate resin is preferably 15 ppm by mass or more, more preferably 20 ppm by mass or more, and even more preferably 25 ppm by mass or more, and is preferably 70 ppm by mass or less, more preferably 60 ppm by mass or less, even more preferably 55 ppm by mass or less, even more preferably 50 ppm by mass or less, even more preferably 40 ppm by mass or less, even more preferably 35 ppm by mass or less, and especially more preferably 30 ppm by mass or less. By making it equal to or more than the lower limit, the flowability tends to be improved, and the availability of the recycled polycarbonate resin tends to be improved. In addition, by making it equal to or less than the upper limit, the flame retardancy tends to be further improved, and the amount of generated gas tends to be reduced. In addition, from the viewpoint of the balance between the availability, ease of production, and quality stability of the recycled polycarbonate resin, it is preferable to make it within the upper and lower limits. The content of bisphenol A in the recycled polycarbonate resin is measured according to the description in the Examples section described later.
[0035] The branch amount of the recycled polycarbonate resin used in this embodiment is 50 to 3500 mass ppm. The branch amount of the recycled polycarbonate resin is preferably 100 mass ppm or more, more preferably 200 mass ppm or more, even more preferably 500 mass ppm or more, even more preferably 1000 mass ppm or more, even more preferably 1500 mass ppm or more, even more preferably 2000 mass ppm or more, and preferably 3000 mass ppm or less, more preferably 2500 mass ppm or less. By making it equal to or more than the lower limit, the dripping prevention effect during combustion tends to be improved. In addition, by making it equal to or less than the upper limit, the decomposition of the resin due to the transesterification of the polyalkylene terephthalate resin and the polycarbonate resin tends to be suppressed, the crystallization temperature tends to be increased, the combustion time tends to be shortened, and the amount of generated gas tends to be reduced. The branching amount of the recycled polycarbonate resin is measured according to the description in the Examples section described later.
[0036] The recycled polycarbonate resin used in this embodiment may contain one or more structural units represented by formulae (C1) to (C4). [ka]
[0037] The branch amount of the recycled polycarbonate resin used in this embodiment is 50 to 3500 mass ppm. The branch amount of the recycled polycarbonate resin is preferably 100 mass ppm or more, more preferably 200 mass ppm or more, even more preferably 500 mass ppm or more, even more preferably 1000 mass ppm or more, even more preferably 1500 mass ppm or more, even more preferably 2000 mass ppm or more, and preferably 3000 mass ppm or less, more preferably 2500 mass ppm or less. By making it equal to or more than the lower limit, the dripping prevention effect during combustion tends to be improved. In addition, by making it equal to or less than the upper limit, the decomposition of the resin due to the transesterification of the polyalkylene terephthalate resin and the polycarbonate resin tends to be suppressed, the crystallization temperature tends to be increased, the combustion time tends to be shortened, and the amount of generated gas tends to be reduced. The branching amount of the recycled polycarbonate resin is measured according to the description in the Examples section described later.
[0038] The recycled polycarbonate resin used in this embodiment has a PSA content of preferably 5 mass ppm or more, more preferably 30 mass ppm or more, even more preferably 50 mass ppm or more, even more preferably 100 mass ppm or more, even more preferably 200 mass ppm or more, and preferably 700 mass ppm or less, more preferably 600 mass ppm or less, even more preferably 500 mass ppm or less, even more preferably 380 mass ppm or less, and even more preferably 350 mass ppm or less, when it is hydrolyzed. By making it equal to or more than the lower limit, the dripping prevention effect during the combustion test tends to be improved. In addition, by making it equal to or less than the upper limit, the decomposition of the resin due to the transesterification of the polyalkylene terephthalate resin and the polycarbonate resin tends to be suppressed, the thermal stability tends to be excellent, the combustion time tends to be shortened, and the amount of generated gas tends to be reduced.
[0039] The recycled polycarbonate resin used in this embodiment, when hydrolyzed, has a PSA-Me content of 10 mass ppm or more, more preferably 50 mass ppm or more, more preferably 150 mass ppm or more, even more preferably 300 mass ppm or more, even more preferably 500 mass ppm or more, and preferably 2000 mass ppm or less, more preferably 1500 mass ppm or less, even more preferably 1000 mass ppm or less, even more preferably 900 mass ppm or less, and even more preferably 800 mass ppm or less, based on 100 mass parts of recycled polycarbonate. By making it equal to or more than the lower limit, the dripping prevention effect during the combustion test tends to be improved. In addition, by making it equal to or less than the upper limit, the decomposition of the resin due to the transesterification of the polyalkylene terephthalate resin and the polycarbonate resin tends to be suppressed, the thermal stability tends to be excellent, the combustion time tends to be shortened, and the amount of generated gas tends to be reduced.
[0040] The recycled polycarbonate resin used in this embodiment may have a PBA content of 0 parts by mass or more relative to 100 parts by mass of recycled polycarbonate when hydrolyzed, preferably 0.01 ppm by mass or more, more preferably 10 ppm by mass or more, more preferably 30 ppm by mass or more, even more preferably 100 ppm by mass or more, even more preferably 400 ppm by mass or more, and preferably 2000 ppm by mass or less, more preferably 1500 ppm by mass or less, even more preferably 1000 ppm by mass or less, even more preferably 900 ppm by mass or less, and even more preferably 800 ppm by mass or less. By setting the content to the lower limit or more, the dripping prevention effect during the combustion test tends to be improved. In addition, by setting the content to the upper limit or less, the decomposition of the resin due to the transesterification of the polyalkylene terephthalate resin and the polycarbonate resin tends to be suppressed, the thermal stability tends to be excellent, the combustion time tends to be shortened, and the amount of generated gas tends to be reduced.
[0041] The recycled polycarbonate resin used in this embodiment, when hydrolyzed, has a content of dicarboxylic acid (two dicarboxylic acids DA1 and DA2 described later) of 1 mass ppm or more, more preferably 10 mass ppm or more, even more preferably 100 mass ppm or more, even more preferably 200 mass ppm or more, even more preferably 300 mass ppm or more, and preferably 1500 mass ppm or less, more preferably 1000 mass ppm or less, even more preferably 900 mass ppm or less, even more preferably 800 mass ppm or less, and even more preferably 700 mass ppm or less. By making it equal to or more than the lower limit, the dripping prevention effect during the combustion test tends to be improved. In addition, by making it equal to or less than the upper limit, the decomposition of the resin due to the transesterification of the polyalkylene terephthalate resin and the polycarbonate resin tends to be suppressed, the thermal stability tends to be excellent, the combustion time tends to be shortened, and the amount of generated gas tends to be reduced.
[0042] [ka]
[0043] The contents of PSA, PSA-Me, PBA, and dicarboxylic acids (DA1, DA2) generated by hydrolysis of the recycled polycarbonate resin are measured according to the description in the examples described later.
[0044] The resin composition of the present embodiment has a melt volume rate (MVR) of 2 to 11 cm3, measured according to ISO1133 at 300°C and a load of 1.20 kgf for the recycled polycarbonate resin. 3 / 10 minutes is preferred. The MVR of the recycled polycarbonate resin is 3 cm 3 / 10 minutes or more is preferable, and 4cm 3 / 10 minutes or more is more preferable, and 5 cm 3 / 10 minutes or more is more preferable, and 10 cm 3 / 10 minutes or less is preferable, and 9cm 3 / 10 minutes or less is more preferable, and 8 cm 3 / 10 minutes or less is more preferable, and 7 cm 3 It is more preferable that the viscosity is 100 / min or less. By making the viscosity equal to or more than the lower limit, the flowability tends to be improved. Also, by making the viscosity equal to or less than the upper limit, the mechanical properties tend to be improved, and the impact resistance tends to be improved. The resin composition of the present embodiment may contain only one type of recycled polycarbonate resin, or may contain two or more types. When two or more types are contained, it is preferable that the MVR of the mixture is in the above range.
[0045] The polydispersity (Mw / Mn) of the recycled polycarbonate resin is preferably 2.6 or more, and is preferably 3.5 or less, and more preferably 3.3 or less. The polydispersity of the recycled polycarbonate resin is measured according to the description of the examples described later.
[0046] Recycled polycarbonate resin usually has a higher metal element content than virgin products due to the resin consumption and recycling process. However, even recycled polycarbonate resin may not have a high metal element content. From the viewpoint of availability, ease of production, and quality stability of the recycled polycarbonate resin, the recycled polycarbonate resin used in this embodiment preferably has an aluminum element content of 0.2 to 1000 mass ppm relative to 100 parts by mass of the recycled polycarbonate resin. Furthermore, the aluminum element content is preferably 0.3 mass ppm or more, more preferably 0.5 mass ppm or more, even more preferably 1 mass ppm or more, even more preferably 2 mass ppm or more, even more preferably 5 mass ppm or more, even more preferably 7 mass ppm or more, and especially more preferably 8 mass ppm or more, and more preferably 500 mass ppm or less, even more preferably 300 mass ppm or less, even more preferably 100 mass ppm or less, even more preferably 50 mass ppm or less, even more preferably 30 mass ppm or less, even more preferably 15 mass ppm or less, and especially more preferably 10 mass ppm or less. By setting the content to be equal to or more than the lower limit, the laser marking property tends to be improved, whereas by setting the content to be equal to or less than the upper limit, the insulating properties such as the dielectric breakdown strength tend to be improved, the tracking resistance tends to be improved, and the amount of gas generated tends to be reduced.
[0047] From the viewpoint of availability, ease of production, and quality stability of the recycled polycarbonate resin, in this embodiment, it is preferable that the recycled polycarbonate resin contains iron element at a ratio of 0.2 to 100 mass ppm relative to the polycarbonate resin. The content of the iron element is more preferably 0.8 mass ppm or more, even more preferably 1 mass ppm or more, even more preferably 2 mass ppm or more, even more preferably 3 mass ppm or more, even more preferably 4 mass ppm or more, and more preferably 50 mass ppm or less, even more preferably 35 mass ppm or less, even more preferably 20 mass ppm or less, even more preferably 15 mass ppm or less, even more preferably 10 mass ppm or less, and particularly more preferably 8 mass ppm or less. By making it equal to or more than the lower limit, the laser marking property tends to be improved. Also, by making it equal to or less than the upper limit, the insulating property such as dielectric breakdown strength tends to be further improved, the tracking resistance tends to be improved, and the amount of generated gas tends to be reduced.
[0048] From the viewpoint of availability, ease of production, and quality stability of the recycled polycarbonate resin, in this embodiment, it is preferable that the recycled polycarbonate resin contains phosphorus element at a ratio of 1 to 200 mass ppm relative to the polycarbonate resin. The content of the phosphorus element is more preferably 2 mass ppm or more, even more preferably 3 mass ppm or more, even more preferably 4 mass ppm or more, even more preferably 5 mass ppm or more, and more preferably 150 mass ppm or less, even more preferably 100 mass ppm or less, even more preferably 50 mass ppm or less, and even more preferably 10 mass ppm or less. By making it equal to or more than the lower limit, transesterification of the mixture of the polyalkylene terephthalate resin and the recycled polycarbonate resin is suppressed, and the heat resistance of the resin tends to be improved. In addition, by making it equal to or less than the upper limit, insulation properties such as dielectric breakdown strength tend to be further improved, the amount of generated gas tends to be reduced, and hydrolysis resistance tends to be improved.
[0049] The resin composition of the present embodiment may contain only recycled polycarbonate resin as the polycarbonate resin, or may contain virgin polycarbonate resin in addition to recycled polycarbonate resin. The content of the recycled polycarbonate resin in the resin composition of the present embodiment is preferably 50 parts by mass or more, more preferably 60 parts by mass or more, even more preferably 70 parts by mass or more, even more preferably 80 parts by mass or more, and even more preferably 90 parts by mass or more, and is 100 parts by mass or less, in 100 parts by mass of the polycarbonate resin. By making it equal to or more than the lower limit, recyclability is improved. By making it equal to or less than the upper limit, production stability and quality stability tend to be further improved.
[0050] <Blend ratio of polyalkylene terephthalate resin and polycarbonate resin> In the resin composition of the present embodiment, the mass ratio of the polyalkylene terephthalate resin (preferably the polybutylene terephthalate resin) and the polycarbonate resin in a total of 100 parts by mass is 80 / 20 to 20 / 80, and preferably 30 / 70 to 55 / 45. By using such a blend ratio, a molded product having excellent physical properties can be obtained. The blend ratio is preferably such that the proportion of polyalkylene terephthalate resin in a total of 100 parts by mass of polyalkylene terephthalate resin and polycarbonate resin is 35 parts by mass or more, more preferably 40 parts by mass or more, and even more preferably 45 parts by mass or more, and is preferably 50 parts by mass or less, and more preferably 49 parts by mass or less. The resin composition of the present embodiment may contain only one type of polyalkylene terephthalate resin and one type of polycarbonate resin, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.
[0051] The total amount of the polyalkylene terephthalate resin (preferably polybutylene terephthalate resin) and the polycarbonate resin (preferably recycled polycarbonate resin) in the resin composition of this embodiment is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, even more preferably 40% by mass or more, even more preferably 45% by mass or more, and also preferably 90% by mass or less, more preferably 80% by mass or less, even more preferably 70% by mass or less, even more preferably 60% by mass or less, and even more preferably 55% by mass or less. By making it equal to or more than the lower limit, moldability tends to be improved, nominal fracture strain tends to be improved, and impact resistance tends to be improved. In addition, by making it equal to or less than the upper limit, the appearance of the molded product tends to be improved, and flame retardancy tends to be improved.
[0052] <Elastomer> The resin composition of the present embodiment contains an elastomer. By containing an elastomer, the impact resistance of the obtained molded article tends to be further improved. The type of elastomer is not particularly limited, and any known elastomer can be used.
[0053] An example of an elastomer is an elastomer containing an epoxy group. By including an elastomer containing an epoxy group, the affinity with the polybutylene terephthalate resin tends to be high, and a molded product having high impact resistance tends to be obtained.
[0054] A first embodiment of the elastomer containing an epoxy group is a copolymer obtained by copolymerizing an α-olefin, a glycidyl ester of an α,β-unsaturated acid, and, if necessary, an unsaturated monomer copolymerizable therewith. It is preferable to use 60 mass% or more of the α-olefin and the glycidyl ester of an α,β-unsaturated acid among all the copolymerization components in the copolymer.
[0055] Examples of α-olefins include ethylene, propylene, butene-1, and pentene-1. Two or more of these may be used. Examples of glycidyl esters of α,β-unsaturated acids include glycidyl acrylate, glycidyl methacrylate, glycidyl ethacrylate, and glycidyl itaconate. Two or more of these may be used. Examples of vinyl monomers copolymerizable with the above components include vinyl ethers, vinyl esters such as vinyl acetate and vinyl propionate, acrylic and methacrylic esters such as methyl, ethyl, propyl, and butyl, acrylonitrile, and styrene. Two or more of these may be used.
[0056] Preferred examples of the epoxy group-containing elastomer of the first embodiment include ethylene / glycidyl methacrylate copolymer, ethylene / glycidyl methacrylate / vinyl acetate copolymer, ethylene / glycidyl methacrylate / alkyl acrylate copolymer, ethylene / alkyl acrylate / vinyl acetate copolymer, etc. In particular, from the viewpoint of excellent toughness and further improving the wet heat resistance and impact resistance of the molded product, ethylene / glycidyl methacrylate / alkyl acrylate (preferably butyl acrylate) copolymer is preferred. Specific examples of the epoxy group-containing elastomer of the first embodiment are available under the trade names "Rotader" (registered trademark) AX8900 and AX8700 manufactured by Arkema.
[0057] A second embodiment of the elastomer containing epoxy groups is a core-shell type elastomer. By using a core-shell type elastomer, the molecular particle size is small, so that it is easy to disperse in polybutylene terephthalate resin, and the welding strength tends to increase due to the reaction of the reactive groups. An example of a core-shell type elastomer is one in which a monomer component is graft-copolymerized onto a core polymer. The core is preferably a rubber polymer, examples of which include acrylonitrile-acrylic rubber polymer-styrene graft copolymer (ASA resin), methyl methacrylate-acrylic rubber polymer-styrene graft copolymer (MSA resin), methyl methacrylate-acrylonitrile-acrylic rubber polymer-styrene graft copolymer (MASA resin), polyorganosiloxane-containing rubber polymer, and the like, with polyorganosiloxane-containing rubber polymer being preferred. The polyorganosiloxane-containing rubbery polymer generally has a glass transition temperature of 0° C. or lower, preferably −20° C. or lower, and more preferably −30° C. or lower. Specific examples of the rubber component are not particularly limited as long as they contain polyorganosiloxane rubber, and examples thereof include polyorganosiloxane rubber, and composite rubber (IPN type) of polyorganosiloxane rubber and polyalkyl acrylate rubber.
[0058] Specific examples of the monomer component graft copolymerizable with the core include aromatic vinyl compounds, vinyl cyanide compounds, (meth)acrylic acid ester compounds, (meth)acrylic acid compounds, epoxy group-containing (meth)acrylic acid ester compounds such as glycidyl (meth)acrylate, maleimide compounds such as maleimide, N-methylmaleimide, and N-phenylmaleimide, α,β-unsaturated carboxylic acid compounds such as maleic acid, phthalic acid, and itaconic acid, and anhydrides thereof (for example, maleic anhydride, etc.).
[0059] Specific examples of rubber polymers, aromatic vinyl compounds, vinyl cyanide compounds, and (meth)acrylic acid ester compounds are described in paragraphs 0042 to 0046 of JP 2019-059813 A, the contents of which are incorporated herein by reference.
[0060] The epoxy group-containing elastomer of the second embodiment is preferably a compound obtained by graft polymerizing an epoxy group-containing (meth)acrylic acid ester compound onto a polyorganosiloxane-containing rubbery polymer (preferably a composite rubber of a polyorganosiloxane rubber and a polyalkyl acrylate rubber).
[0061] Specific examples of the elastomer containing an epoxy group according to the second embodiment include "Metablen (registered trademark, the same applies below) S-2002" and "Metablen S-2200" manufactured by Mitsubishi Rayon Co., Ltd.
[0062] Another example of the elastomer is a graft copolymer obtained by graft-copolymerizing a rubber component with a monomer component copolymerizable therewith. The method for producing the graft copolymer may be any of bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc., and the copolymerization method may be one-stage grafting or multi-stage grafting.
[0063] The rubber component usually has a glass transition temperature of 0° C. or lower, preferably -20° C. or lower, and more preferably -30° C. or lower. Specific examples of the rubber component include polybutadiene rubber, polyisoprene rubber, polyalkyl acrylate rubber such as polybutyl acrylate, poly(2-ethylhexyl acrylate), and butyl acrylate-2-ethylhexyl acrylate copolymer, silicone rubber such as polyorganosiloxane rubber, butadiene-acrylic composite rubber, IPN (Interpenetrating Polymer Network) type composite rubber consisting of polyorganosiloxane rubber and polyalkyl acrylate rubber, styrene-butadiene rubber, ethylene-α-olefin rubber such as ethylene-propylene rubber, ethylene-butene rubber, and ethylene-octene rubber, ethylene-acrylic rubber, and fluororubber. These may be used alone or in combination of two or more. Among these, polybutadiene rubber, polyalkyl acrylate rubber, polyorganosiloxane rubber, IPN type composite rubber consisting of polyorganosiloxane rubber and polyalkyl acrylate rubber, and styrene-butadiene rubber are preferred from the standpoint of mechanical properties and surface appearance.
[0064] Specific examples of the monomer component capable of graft copolymerization with the rubber component include the epoxy group-containing elastomer, and are the same as the specific examples of the monomer component capable of graft copolymerization with the rubber component described above.
[0065] The graft copolymer obtained by copolymerizing a rubber component is preferably a core / shell type graft copolymer in terms of impact resistance and surface appearance. Among them, a core / shell type graft copolymer is particularly preferred, which is made of at least one rubber component selected from polybutadiene-containing rubber, polybutyl acrylate-containing rubber, polyorganosiloxane rubber, and an IPN type composite rubber consisting of polyorganosiloxane rubber and polyalkyl acrylate rubber, and a shell layer formed by copolymerizing (meth)acrylic acid ester around the core layer. The above-mentioned core / shell type graft copolymer preferably contains 40% by mass or more of the rubber component, more preferably 60% by mass or more. In addition, it is preferable that the (meth)acrylic acid is contained in an amount of 10% by mass or more. In this embodiment, the core / shell type does not necessarily have to be one in which the core layer and the shell layer can be clearly distinguished, and is intended to broadly include a compound obtained by graft polymerizing a rubber component around a core portion.
[0066] Preferable specific examples of these core / shell type graft copolymers include methyl methacrylate-butadiene-styrene copolymer (MBS), methyl methacrylate-acrylonitrile-butadiene-styrene copolymer (MABS), methyl methacrylate-butadiene copolymer (MB), methyl methacrylate-acrylic rubber copolymer (MA), methyl methacrylate-acrylic rubber-styrene copolymer (MAS), methyl methacrylate-acrylic-butadiene rubber copolymer, methyl methacrylate-acrylic-butadiene rubber-styrene copolymer, methyl methacrylate-(acrylic-silicone IPN rubber) copolymer, etc. Such rubbery polymers may be used alone or in combination of two or more.
[0067] Examples of such elastomers include "PARALOID (registered trademark, the same applies below) EXL2602", "PARALOID EXL2603", "PARALOID EXL2655", "PARALOID EXL2311", "PARALOID EXL2313", "PARALOID EXL2315", "PARALOID KM330", "PARALOID KM336P", and "PARALOID KCZ201" manufactured by Rohm and Haas Japan Co., Ltd.; "METABLEN (registered trademark, the same applies below) C-223A", "METABLEN E-901", "METABLEN S-2001", and "METABLEN SRK-200" manufactured by Mitsubishi Rayon Co., Ltd.; "KANE ACE (registered trademark, the same applies below) M-511", "KANE ACE M-600", "KANE ACE M-400", "KANE ACE M-580", "KANE ACE M-711", and "KANE ACE MR-01" manufactured by Kaneka Corporation; and "UBESTA XPA" manufactured by Ube Industries, Ltd.
[0068] Another example of the elastomer is an acrylic block copolymer. An example of the acrylic block copolymer is a block copolymer containing a hard segment made of a methyl methacrylate block and a soft segment made of an alkyl acrylate block.
[0069] The acrylic block copolymer is preferably a triblock copolymer having two blocks constituting a hard segment on both sides of one block constituting a soft segment, or a diblock copolymer having one block constituting a soft segment and one block constituting a hard segment. That is, the acrylic block copolymer in this embodiment preferably has a triblock structure consisting of a methyl methacrylate block-alkyl acrylate block-methyl methacrylate block, or a diblock structure consisting of a methyl methacrylate block-alkyl acrylate block.
[0070] Examples of alkyl acrylates constituting the soft segment include n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, n-hexyl acrylate, cyclohexyl acrylate, n-heptyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, dodecyl acrylate, phenyl acrylate, toluyl acrylate, benzyl acrylate, isobornyl acrylate, 2-methoxyethyl acrylate, 3-methoxybutyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, stearyl acrylate, glycidyl acrylate, 2-aminoethyl acrylate, γ-(acryloyloxypropyl)trimethacrylate, Examples of the acrylates include xysilane, γ-(acryloyloxypropyl)dimethoxymethylsilane, ethylene oxide adduct of acrylic acid, trifluoromethylmethyl acrylate, 2-trifluoromethylethyl acrylate, 2-perfluoroethylethyl acrylate, 2-perfluoroethyl-2-perfluorobutylethyl acrylate, 2-perfluoroethyl, perfluoromethyl acrylate, diperfluoromethylmethyl acrylate, 2-perfluoromethyl-2-perfluoroethylmethyl acrylate, 2-perfluorohexylethyl acrylate, 2-perfluorodecylethyl acrylate, and 2-perfluorohexadecylethyl acrylate, and among these, butyl acrylate or butyl acrylate / 2-ethylhexyl acrylate is preferred.
[0071] The acrylic block copolymer is not particularly limited as long as it can exhibit the effects of the present invention. Among the above, it is preferable that the acrylic block copolymer has a diblock structure consisting of a methyl methacrylate block-butyl acrylate block or a methyl methacrylate block-butyl acrylate / 2-ethylhexyl acrylate block, or a triblock structure consisting of a methyl methacrylate block-butyl acrylate block-methyl methacrylate block or a methyl methacrylate block-butyl acrylate / 2-ethylhexyl acrylate block-methyl methacrylate block.
[0072] In the acrylic block copolymer, the ratio of the hard segment to the soft segment is preferably in the range of 3:97 to 40:60 on a mass basis, more preferably 5:95 to 35:65. The higher the ratio of the soft segment, the more the vinyl chloride resin can be softened, but if the ratio of the hard segment is too low, the compatibility with the vinyl chloride resin decreases as described above, and the moldability deteriorates. On the other hand, the lower the ratio of the soft segment, the lower the efficiency of softening the vinyl chloride resin.
[0073] Examples of commercially available acrylic block copolymers include LA1892, LA4285, LA2270, LA2250, LA2140, LA2330, and LA3320, which are part of the LA series of Kuraray Co., Ltd.'s Kuralyte (registered trademark), and M51, M52, and M22, which are part of the Nanostrength (registered trademark) series of ARKEMA Co., Ltd. In addition, acrylic copolymers using butyl acrylate / 2-ethylhexyl acrylate in the soft segment are commercially available as LK9243, KL-LK9333, and the like, which are part of the LK series of Kuraray Co., Ltd.'s Kuralyte (registered trademark).
[0074] The elastomer used in the present embodiment preferably has a melt mass flow rate (MFR) measured in accordance with ISO1133 under conditions of 190°C and a load of 2.16 kgf of 1 g / 10 min or more, more preferably 2 g / 10 min or more, and preferably 15 g / 10 min or less, and even more preferably 10 g / 10 min or less. When the resin composition of the present embodiment contains two or more types of elastomers, the MFR of the elastomers is a weighted average value.
[0075] In addition to the above, the elastomers that can be used include the elastomers described in paragraphs 0075 to 0088 of JP 2012-251061 A, the elastomers described in paragraphs 0101 to 0107 of JP 2012-177047 A, the elastomers described in paragraphs 0076 to 0087 of JP 2016-98242 A, and the elastomers described in paragraphs 0080 to 0087 of JP 2019-11514 A, and the like, the contents of which are incorporated herein by reference.
[0076] The content of the elastomer in the resin composition of the present embodiment is 3 parts by mass or more, preferably 5 parts by mass or more, more preferably 7 parts by mass or more, even more preferably 8 parts by mass or more, and even more preferably 9 parts by mass or more, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the polycarbonate resin, and is 30 parts by mass or less, preferably 25 parts by mass or less, more preferably 20 parts by mass or less, even more preferably 20 parts by mass or less, even more preferably 15 parts by mass or less, and may be 12 parts by mass or less. By making it equal to or more than the lower limit, the impact resistance tends to be further improved. By making it equal to or less than the upper limit, the flowability tends to be improved and high flame retardancy tends to be easily exhibited. The resin composition of the present embodiment may contain only one type of elastomer, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0077] <Flame retardants> The resin composition of the present embodiment contains a flame retardant. By containing the flame retardant, flame retardancy can be achieved. Examples of flame retardants include halogen-based flame retardants, phosphorus-based flame retardants (metal phosphinate, melamine polyphosphate, etc.), nitrogen-based flame retardants (melamine cyanurate, etc.), and metal hydroxides (magnesium hydroxide, etc.). Phosphorus-based flame retardants and halogen-based flame retardants are preferred, and halogen-based flame retardants are more preferred. As phosphorus-based flame retardants, metal phosphinate is more preferred. As halogen-based flame retardants, bromine-based flame retardants are more preferred.
[0078] When a brominated flame retardant is used as the flame retardant, the type is not particularly limited, but brominated phthalimide, brominated poly(meth)acrylate, brominated polycarbonate, brominated epoxy, and brominated polystyrene are preferred, brominated polycarbonate, brominated poly(meth)acrylate, and brominated epoxy are more preferred, and brominated polycarbonate is even more preferred.
[0079] The brominated phthalimide is preferably one represented by the formula (1). [ka] (In formula (1), D represents an alkylene group, an arylene group, -S(=O)2-, -C(=O)-, and a group formed by combining two or more of -O-. i is an integer of 1 to 4.)
[0080] In formula (1), D represents a group consisting of a combination of two or more of an alkylene group, an arylene group, -S(=O)2-, -C(=O)-, and -O-. A group consisting of a combination of an alkylene group or an arylene group and at least one of -S(=O)2-, -C(=O)-, and -O- is preferable, a group consisting of a combination of an alkylene group or an arylene group and one of -S(=O)2-, -C(=O)-, and -O- is more preferable, and an alkylene group is further preferable. The group consisting of a combination of an alkylene group and -O- is intended to include, for example, a combination of two alkylene groups and one -O- (the same applies to other combinations). The alkylene group represented by D is preferably an alkylene group having 1 to 6 carbon atoms, more preferably a methylene group, an ethylene group, a propylene group, or a butylene group. The arylene group is preferably a phenylene group. "i" is an integer of 1 to 4, and is preferably 4.
[0081] Examples of the brominated phthalimide represented by formula (1) include N,N'-(bistetrabromophthalimide)ethane, N,N'-(bistetrabromophthalimide)propane, N,N'-(bistetrabromophthalimide)butane, N,N'-(bistetrabromophthalimide)diethyl ether, N,N'-(bistetrabromophthalimide)dipropyl ether, N,N'-(bistetrabromophthalimide)dibutyl ether, N,N'-(bistetrabromophthalimide)diphenyl sulfone, N,N'-(bistetrabromophthalimide)diphenyl ketone, and N,N'-(bistetrabromophthalimide)diphenyl ether.
[0082] The brominated phthalimide represented by formula (1) is preferably a brominated phthalimide represented by formula (2). [ka] (In formula (2), i is an integer of 1 to 4.) "i" is an integer of 1 to 4, and is preferably 4.
[0083] The brominated poly(meth)acrylate is preferably a polymer obtained by polymerizing a bromine atom-containing benzyl (meth)acrylate alone, copolymerizing two or more kinds of the bromine atom-containing benzyl (meth)acrylate, or copolymerizing the bromine atom with another vinyl monomer, and the bromine atoms are added to a benzene ring with 1 to 5 bromine atoms, preferably 4 to 5 bromine atoms, added per benzene ring.
[0084] Examples of the benzyl acrylate containing a bromine atom include pentabromobenzyl acrylate, tetrabromobenzyl acrylate, tribromobenzyl acrylate, and mixtures thereof. Examples of the benzyl methacrylate containing a bromine atom include methacrylates corresponding to the above-mentioned acrylates.
[0085] Specific examples of other vinyl monomers that can be copolymerized with the bromine atom-containing benzyl (meth)acrylate include acrylic acid, methyl acrylate, ethyl acrylate, butyl acrylate, and benzyl acrylate; methacrylic acid, methyl methacrylate, ethyl methacrylate, butyl methacrylate, and benzyl methacrylate; unsaturated carboxylic acids or anhydrides thereof, such as styrene, acrylonitrile, fumaric acid, and maleic acid; vinyl acetate, and vinyl chloride.
[0086] These are usually used in an equimolar amount or less, particularly preferably 0.5 times the molar amount or less, relative to the bromine atom-containing benzyl (meth)acrylate.
[0087] Furthermore, examples of vinyl monomers that can be used include xylylene diacrylate, xylylene dimethacrylate, tetrabromo xylylene diacrylate, tetrabromo xylylene dimethacrylate, butadiene, isoprene, and divinylbenzene. These can usually be used in an amount of 0.5 or less by mole relative to the bromine atom-containing benzyl acrylate or benzyl methacrylate.
[0088] The brominated poly(meth)acrylate is preferably a polymer obtained by polymerizing a bromine atom-containing (meth)acrylate monomer, particularly benzyl (meth)acrylate, alone or by copolymerizing two or more kinds of the monomers, or by copolymerizing the monomers with other vinyl monomers. The bromine atoms are added to the benzene ring, and the number of added bromine atoms is preferably 1 to 5, more preferably 4 to 5, per benzene ring.
[0089] As the brominated poly(meth)acrylate, pentabromobenzyl poly(meth)acrylate is preferred due to its high bromine content.
[0090] The molecular weight of the brominated poly(meth)acrylate is arbitrary and may be appropriately selected and determined, but the weight average molecular weight (Mw) is preferably 3,000 or more, more preferably 10,000 or more, even more preferably 15,000 or more, even more preferably 20,000 or more, and even more preferably 25,000 or more. By making it equal to or greater than the lower limit, a molded product having higher mechanical strength tends to be obtained. In addition, the upper limit of the weight average molecular weight (Mw) is preferably equal to or less than 100,000, more preferably equal to or less than 80,000, even more preferably equal to or less than 60,000, even more preferably equal to or less than 50,000, and even more preferably equal to or less than 35,000. By making it equal to or less than the upper limit, the flowability of the resin composition tends to be further improved.
[0091] The brominated polycarbonate preferably has a free bromine content of 0.05% by mass or more, and preferably 0.20% by mass or less. By setting the content within such a range, the heat resistance stability of the resin composition tends to be further improved. The brominated polycarbonate also preferably has a chlorine atom content of 0.001% by mass or more, and preferably 0.20% by mass or less. By setting the content within such a range, the mold corrosion resistance during molding tends to be further improved. Specifically, the brominated polycarbonate is preferably a brominated polycarbonate obtained from, for example, brominated bisphenol A, particularly tetrabromobisphenol A. Examples of the terminal structure include a phenyl group, a 4-t-butylphenyl group, and a 2,4,6-tribromophenyl group, and in particular, one having a 2,4,6-tribromophenyl group in the terminal group structure is preferred.
[0092] The average number of carbonate constituent units in the brominated polycarbonate may be appropriately selected and determined, but is preferably 2-30, more preferably 3-15, and even more preferably 3-10.
[0093] The molecular weight of the brominated polycarbonate is optional and may be appropriately selected and determined, but it is preferably from 1,000 to 20,000, more preferably from 2,000 to 10,000, in terms of viscosity average molecular weight.
[0094] The brominated polycarbonate obtained from the above brominated bisphenol A can be obtained, for example, by a conventional method of reacting brominated bisphenol with phosgene. The end-capping agent includes an aromatic monohydroxy compound, which may be substituted with a halogen or an organic group.
[0095] Specific preferred examples of the brominated epoxy include bisphenol A type brominated epoxy compounds, such as tetrabromobisphenol A epoxy compounds and glycidyl brominated bisphenol A epoxy compounds.
[0096] The molecular weight of the brominated epoxy compound is arbitrary and may be appropriately selected and determined, but the weight average molecular weight (Mw) is preferably 3,000 or more, more preferably 10,000 or more, even more preferably 13,000 or more, even more preferably 15,000 or more, and even more preferably 18,000 or more. By making it equal to or more than the lower limit, a molded product having higher mechanical strength tends to be obtained. In addition, the upper limit of the weight average molecular weight (Mw) is preferably 100,000 or less, more preferably 80,000 or less, even more preferably 78,000 or less, even more preferably 75,000 or less, even more preferably 70,000 or less, and may be 50,000 or less, 30,000 or less, or 25,000 or less. By making it equal to or less than the upper limit, the flowability of the resin composition tends to be further improved. The brominated epoxy compound preferably has an epoxy equivalent of 3,000 to 40,000 g / eq, more preferably 4,000 to 35,000 g / eq, and particularly preferably 10,000 to 30,000 g / eq.
[0097] In addition, a brominated epoxy oligomer can be used in combination as the brominated epoxy. In this case, for example, by using an oligomer having Mw of 5,000 or less at a ratio of about 50 mass% or less, the flame retardancy, releasability, and flowability can be appropriately adjusted. The bromine atom content in the brominated epoxy compound is arbitrary, but in order to impart sufficient flame retardancy, it is usually 10 mass% or more, preferably 20 mass% or more, and particularly preferably 30 mass% or more, with the upper limit being 60 mass%, and preferably 55 mass% or less.
[0098] The brominated polystyrene preferably includes a brominated polystyrene containing a constitutional unit represented by the formula (3). [ka] (In formula (3), t is an integer of 1 to 5, and n is the number of constitutional units.)
[0099] Brominated polystyrene may be produced by brominating polystyrene or by polymerizing brominated styrene monomer, but the polymerized brominated styrene has a smaller amount of free bromine (atoms), and is therefore preferred. In formula (3), the CH group to which the brominated benzene is bonded may be substituted with a methyl group. Brominated polystyrene may also be a copolymer in which other vinyl monomers are copolymerized. Examples of the vinyl monomer in this case include styrene, α-methylstyrene, (meth)acrylonitrile, (meth)methyl acrylate, butadiene, and vinyl acetate. Brominated polystyrene may be used alone or as a mixture of two or more types with different structures, and may contain units derived from styrene monomers with different bromine numbers in a single molecular chain.
[0100] Specific examples of brominated polystyrene include poly(4-bromostyrene), poly(2-bromostyrene), poly(3-bromostyrene), poly(2,4-dibromostyrene), poly(2,6-dibromostyrene), poly(2,5-dibromostyrene), poly(3,5-dibromostyrene), poly(2,4,6-tribromostyrene), poly(2,4,5-tribromostyrene), poly(2,3,5-tribromostyrene), and poly(4-bromo-α-methylstyrene). Examples of suitable styrene copolymers include poly(2,4-dibromostyrene), poly(2,5-dibromo-α-methylstyrene), poly(2,4,6-tribromo-α-methylstyrene) and poly(2,4,5-tribromo-α-methylstyrene), of which poly(2,4,6-tribromostyrene), poly(2,4,5-tribromostyrene) and polydibromostyrene and polytribromostyrene containing an average of 2 to 3 bromine groups in the benzene ring are particularly preferred.
[0101] The number n (average degree of polymerization) of the constituent units in the formula (3) of the brominated polystyrene is preferably 30 to 1,500, more preferably 150 to 1,000, and particularly preferably 300 to 800. If the average degree of polymerization is less than 30, blooming is likely to occur, while if it exceeds 1,500, poor dispersion is likely to occur and mechanical properties are likely to deteriorate. The weight-average molecular weight (Mw) of the brominated polystyrene is preferably 5,000 to 500,000, more preferably 10,000 to 500,000, even more preferably 10,000 to 300,000, even more preferably 10,000 to 100,000, and even more preferably 10,000 to 70,000. In particular, in the case of the above-mentioned brominated polystyrene, the weight average molecular weight (Mw) is preferably 50,000 to 70,000, and in the case of brominated polystyrene produced by a polymerization method, the weight average molecular weight (Mw) is preferably about 10,000 to 30,000.
[0102] The bromine concentration (Br content in the examples described later) in the bromine-based flame retardant is preferably 45% by mass or more, more preferably 48% by mass or more, and even more preferably 50% by mass or more. By making it equal to or more than the lower limit, the flame retardancy of the molded article tends to be effectively improved. The upper limit of the bromine concentration is preferably 75% by mass or less, more preferably 73% by mass or less, even more preferably 71% by mass or less, and may be 65% by mass or less.
[0103] When a metal phosphinate is used as a flame retardant, the type is not particularly limited, but it is preferable that the metal phosphinate has an anion portion represented by formula (4) or formula (5) and a metal ion of the cation portion is any one of calcium, magnesium, aluminum, and zinc.
[0104] [ka] (In the formula, R 1 and R 2 each independently represents an alkyl group having 1 to 6 carbon atoms or an aryl group which may have a substituent; R 1 may be the same or different, R 3 represents an alkylene group having 2 to 10 carbon atoms, an arylene group which may have a substituent, or a group consisting of a combination thereof; R 3 may be the same or different, and n represents an integer of 0 to 2.) The aryl group which may have a substituent is preferably a phenyl group which may have a substituent. When it has a substituent, it is preferably an alkyl group having 1 to 3 carbon atoms. It is also preferably unsubstituted. The arylene group which may have a substituent is preferably a phenylene group which may have a substituent. The arylene group which may have a substituent is preferably unsubstituted or has an alkyl group having 1 to 3 carbon atoms (preferably a methyl group) as a substituent. In this embodiment, a metal phosphinate represented by formula (5) is preferred. Also, in this embodiment, aluminum phosphinate is preferred.
[0105] Specific examples of the metal phosphinate include calcium dimethylphosphinate, magnesium dimethylphosphinate, aluminum dimethylphosphinate, zinc dimethylphosphinate, calcium ethylmethylphosphinate, magnesium ethylmethylphosphinate, aluminum ethylmethylphosphinate, zinc ethylmethylphosphinate, calcium diethylphosphinate, magnesium diethylphosphinate, aluminum diethylphosphinate, zinc diethylphosphinate, calcium methyl-n-propylphosphinate, magnesium methyl-n-propylphosphinate, aluminum methyl-n-propylphosphinate, zinc methyl-n-propylphosphinate, and calcium methanedi(methylphosphinate). Examples of such compounds include magnesium methane di(methylphosphinate), aluminum methane bis(methylphosphinate), zinc methane bis(methylphosphinate), calcium benzene-1,4-bis(methylphosphinate), magnesium benzene-1,4-bis(methylphosphinate), aluminum benzene-1,4-bis(methylphosphinate), zinc benzene-1,4-bis(methylphosphinate), calcium methylphenylphosphinate, magnesium methylphenylphosphinate, aluminum methylphenylphosphinate, zinc methylphenylphosphinate, calcium diphenylphosphinate, magnesium diphenylphosphinate, aluminum diphenylphosphinate, and zinc diphenylphosphinate. For details about the metal phosphinate, reference can be made to paragraphs 0052 to 0058 of WO 2010 / 010669, the contents of which are incorporated herein by reference.
[0106] The content of the flame retardant (preferably a bromine-based flame retardant) in the resin composition of this embodiment is 5 parts by mass or more, preferably 7 parts by mass or more, more preferably 8 parts by mass or more, and even more preferably 10 parts by mass or more, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the polycarbonate resin. By making it equal to or more than the lower limit, the flame retardancy of the obtained molded article tends to be further improved. The upper limit of the content of the flame retardant is 50 parts by mass or less, preferably 45 parts by mass or less, more preferably 40 parts by mass or less, even more preferably 35 parts by mass or less, even more preferably 30 parts by mass or less, even more preferably 25 parts by mass or less, even more preferably 20 parts by mass or less, and especially more preferably 15 parts by mass or less, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the polycarbonate resin. By making it equal to or less than the upper limit, the decrease in the mechanical strength of the obtained molded article can be more effectively suppressed. The resin composition of the present embodiment may contain only one type of flame retardant, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0107] <Flame retardant synergist> The resin composition of the present embodiment may contain a flame retardant auxiliary. By containing the flame retardant auxiliary, the flame retardancy of the molded article can be further improved. The flame retardant auxiliary is particularly preferably used when a halogen-based flame retardant is contained. The flame retardant auxiliary used in the present embodiment is exemplified by antimony compounds, such as antimony trioxide (Sb2O3), antimony tetraoxide (Sb2O4), antimony pentoxide (Sb2O5), and sodium antimonate. In particular, antimony oxide, and particularly antimony trioxide, is preferred from the viewpoint of impact resistance. When a flame retardant auxiliary is blended, it may be blended as a master batch. The content of the antimony compound in the master batch is preferably 30 to 90 mass%, more preferably 40 to 85 mass%, further preferably 50 to 85 mass%, even more preferably 60 to 85 mass%, and still more preferably 70 to 85 mass%. The resin used in the master batch is preferably a polyester resin, and more preferably a polybutylene terephthalate resin.
[0108] When the resin composition of the present embodiment contains a flame retardant auxiliary (for example, an antimony compound), the content is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 2 parts by mass or more, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the polycarbonate resin. By making the content equal to or more than the lower limit, the flame retardancy tends to be more effectively exhibited. In addition, the upper limit of the content of the antimony compound is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, even more preferably 10 parts by mass or less, even more preferably 8 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the polycarbonate resin. By making the content equal to or less than the upper limit, the mold release property and impact resistance of the obtained molded product tend to be improved. The resin composition of the present embodiment may contain only one type of flame retardant auxiliary, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0109] <Anti-drip agent> The resin composition of this embodiment may contain an anti-dripping agent. As the anti-dripping agent, polytetrafluoroethylene (PTFE) is preferred, and it is preferred that the anti-dripping agent has a fibril-forming ability, is easily dispersed in the resin composition, and tends to form a fibrous network structure in the resin. As the PTFE that tends to have a fibril-forming ability in the resin composition of this embodiment, a suspension polymerization product can be mentioned. In addition, as the PTFE, it is preferred to use a product with reduced perfluorooctanoic acid (PFOA) or a product that does not contain PFOA, from the viewpoint of reducing the environmental load. The content of the anti-dripping agent is preferably 0.1 to 20 parts by mass relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the polycarbonate resin, more preferably 0.2 parts by mass or more, even more preferably 0.3 parts by mass or more, even more preferably 0.4 parts by mass or more, more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and even more preferably 1 part by mass or less. By making it equal to or more than the lower limit, dripping during combustion tends to be suppressed and impact resistance tends to be improved. Also, by making it equal to or less than the upper limit, the appearance of the molded product tends to be improved and the flowability tends to be improved. The resin composition of the present embodiment may contain only one type of anti-dripping agent, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0110] <Interesterification inhibitor> The resin composition of the present embodiment may contain an ester exchange inhibitor. By containing an ester exchange inhibitor, a resin composition or a molded article having excellent thermal stability can be obtained. As an example of the transesterification inhibitor, phosphate and / or phosphoric acid are preferable. Phosphates include zinc phosphate, phosphates of group 1 or group 2 metals, and metal salts of organic phosphates. Phosphates include organic phosphates, which are preferable because they tend to reduce the amount of gas generated, tend to improve the appearance of molded products, tend to increase the crystallization temperature, and tend to improve releasability.
[0111] In this embodiment, the phosphate preferably contains at least one of a compound represented by formula (P1) and a compound represented by formula (P2). Formula (P1) Formula (P2) [ka] (In formula (P1) and formula (P2), R x each independently represents a linear or branched alkyl group having 3 to 30 carbon atoms.
[0112] R x The number of carbon atoms in the alkyl group is preferably 8 or more, more preferably 13 or more, and even more preferably 15 or more, and is preferably 25 or less, more preferably 20 or less, even more preferably 18 or less, and most preferably 18. R x is a straight-chain or branched alkyl group, but is preferably a straight-chain alkyl group.
[0113] In this embodiment, it is more preferable that the phosphate contains at least one of the compounds represented by formula (P1-1) and (P2-1). In this embodiment, a mixture of the compounds represented by formula (P1-1) and (P2-1) is more preferable. Formula (P1-1) Formula (P2-1) [ka]
[0114] The phosphoric acid preferably contains at least one compound represented by formula (P3). Formula (P3) [ka] (In formula (P3), R represents a linear or branched alkyl group having 2 to 18 carbon atoms. nx represents 1 or 2.) The number of carbon atoms in R is preferably 8 or more, more preferably 13 or more, and even more preferably 15 or more, and is preferably 25 or less, more preferably 20 or less, even more preferably 18 or less, and most preferably 18. R is a straight-chain or branched alkyl group, preferably a straight-chain alkyl group.
[0115] nx is 1 or 2, and is preferably a mixture of 1 and 2.
[0116] The transesterification inhibitor may be a commercially available product, and examples thereof include AX-71 manufactured by ADEKA Corporation, and JP-518Zn manufactured by Johoku Chemical Co., Ltd.
[0117] The content of the transesterification inhibitor in the resin composition of this embodiment is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the polycarbonate resin, and is preferably 2 parts by mass or less, more preferably 1.5 parts by mass or less, even more preferably 1 part by mass or less, even more preferably 0.8 parts by mass or less, and may be 0.5 parts by mass or less. By making it equal to or more than the lower limit, the effect of suppressing thermal deterioration and oxidative deterioration of the resin during melt kneading, molding, and use as a molded body tends to be improved, discoloration of the resin tends to be more effectively suppressed, flame retardancy tends to be improved, the crystallization temperature tends to be higher, and the appearance of the molded product tends to be improved. By making it equal to or less than the upper limit, it tends to be possible to effectively suppress adverse effects on the appearance and physical properties due to aggregation of additives such as stabilizers. The resin composition of the present embodiment may contain only one type of transesterification inhibitor, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0118] <Non-fibrous inorganic filler> The resin composition of the present embodiment preferably contains a non-fibrous inorganic filler. By containing a non-fibrous inorganic filler, the physical properties and heat resistance are improved, and the effect of reducing the anisotropy of shrinkage during molding is improved. The non-fibrous inorganic filler means a filler having a shape other than fibers, and a plate-like filler or a particulate filler is preferred. Examples of non-fibrous inorganic fillers include calcium carbonate, talc, mica, silica, kaolin, wollastonite, barium sulfate, zirconium silicate, clay, bentonite, hydrotalcite, calcium sulfate, barium carbonate, magnesium carbonate, magnesium sulfate, calcium silicate, alumina, glass beads, glass flakes, titanium oxide, zinc oxide, magnesium oxide, calcium titanate, magnesium titanate, barium titanate, and the like. Of these, calcium carbonate, talc, mica, silica, kaolin, barium sulfate, zirconium silicate, and titanium oxide are preferred, and calcium carbonate, talc, and titanium oxide are more preferred, with titanium oxide tending to improve impact resistance, flame retardancy, and tracking resistance, and therefore even more preferred. The non-fibrous inorganic filler used in the present embodiment is preferably surface-treated with an acid, a siloxane-based compound, an inorganic compound, etc. In particular, in the case of titanium oxide, it is preferable that the surface is treated with an organosiloxane-based compound or an inorganic compound such as alumina or silica from the viewpoint of thermal stability. Examples of acids used in the acid treatment include fatty acids, rosin acid, and lignic acid, and preferably saturated or unsaturated fatty acids having 6 to 20 carbon atoms. Examples of saturated or unsaturated fatty acids having 6 to 20 carbon atoms include stearic acid, palmitic acid, lauric acid, oleic acid, and linoleic acid.
[0119] The non-fibrous inorganic filler used in this embodiment has an average particle size of preferably 5 μm or less, more preferably 3 μm or less, even more preferably 1 μm or less, even more preferably 0.8 μm or less, even more preferably 0.5 μm or less, and particularly preferably 0.3 μm or less. The lower limit of the average particle size is preferably 0.01 μm or more, more preferably 0.08 μm or more, even more preferably 0.10 μm or more, and even more preferably 0.15 μm or more. The average particle size in this embodiment is the average of particle sizes observed from an enlarged image of a scanning electron microscope. In the case of surface-treated titanium oxide, the primary particle size of titanium oxide after surface treatment is taken as the average particle size.
[0120] The content of the non-fibrous inorganic filler is preferably 1 part by mass or more, more preferably 2 parts by mass or more, even more preferably 3 parts by mass or more, and particularly preferably 3.5 parts by mass or more, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the polycarbonate resin. By making it equal to or more than the lower limit, the impact resistance tends to be improved, the flame retardancy tends to be improved, and the tracking resistance tends to be improved. In addition, the upper limit of the content of the non-fibrous inorganic filler is preferably 12 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 8 parts by mass or less, even more preferably 6 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the polycarbonate resin. By making it equal to or less than the upper limit, the surface appearance of the molded article tends to be improved.
[0121] The content of the non-fibrous inorganic filler in the resin composition of the present embodiment is preferably 0.5% by mass or more of the resin composition, more preferably 1.0% by mass or more, even more preferably 2.0% by mass or more, and even more preferably 2.5% by mass or more. By making it equal to or more than the lower limit, the impact resistance tends to be improved, the flame retardancy tends to be improved, and the tracking resistance tends to be improved. In addition, the content of the non-fibrous inorganic filler in the resin composition of the present embodiment is preferably 50% by mass or less of the resin composition, more preferably 40% by mass or less, even more preferably 30% by mass or less, even more preferably 20% by mass or less, even more preferably 10% by mass or less, even more preferably 7% by mass or less, and particularly preferably 5% by mass or less. By making it equal to or less than the upper limit, the surface appearance of the molded product tends to be better and the flowability tends to be improved. The resin composition of the present embodiment may contain only one type of non-fibrous inorganic filler, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range. In particular, it is preferable to contain 0.5 to 10 parts by mass of rutile-type titanium oxide having an average particle size of 0.15 to 0.4 μm per 100 parts by mass of the total of the polyalkylene terephthalate resin and the polycarbonate resin, as this tends to make it easier to effectively exhibit high levels of flame retardancy, tracking resistance, and impact resistance.
[0122] The resin composition of the present embodiment may or may not further contain a fibrous filler. The resin composition of the present embodiment preferably does not substantially contain a fibrous filler. The term "substantially does not contain" means that the content of the fibrous filler contained in the resin composition of the present embodiment is less than 5% by mass of the resin composition, preferably less than 3% by mass, more preferably less than 1% by mass, and even more preferably less than 0.1% by mass.
[0123] <Antioxidants> The resin composition of the present embodiment may contain an antioxidant. By containing an antioxidant, a resin composition or a molded article having excellent thermal stability can be obtained. The antioxidant preferably contains one or more compounds selected from the group consisting of thioether compounds, hindered phenol compounds, and phosphite compounds, and more preferably contains a hindered phenol compound.
[0124] As the thioether-based compound, any conventionally known sulfur atom-containing compound can be used, and among them, thioethers are preferred. By including the thioether-based compound in the resin composition of the present embodiment, the appearance of the molded product tends to be improved and color change tends to be suppressed. Specific examples include didodecylthiodipropionate, ditetradecylthiodipropionate, dioctadecylthiodipropionate, pentaerythritol tetrakis(3-dodecylthiopropionate), 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-(dodecylthio)propionate], thiobis(N-phenyl-β-naphthylamine), 2-mercaptobenzothiazole, 2-mercaptobenzimidazole, tetramethylthiuram monosulfide, tetramethylthiuram disulfide, nickel dibutyldithiocarbamate, nickel isopropylxanthate, and trilauryltrithiophosphite. Among these, 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-(dodecylthio)propionate] is preferable. Commercially available products include "Seenox 412S" manufactured by Shipro Chemical Co., Ltd. and "Adekastab AO-412S" manufactured by ADEKA Corporation.
[0125] Examples of hindered phenol compounds include pentaerythritol tetrakis (3-(3,5-di-t-butyl-4-hydroxyphenyl) propionate), octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, thiodiethylene bis (3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), pentaerythritol tetrakis (3-(3,5-di-neopentyl-4-hydroxyphenyl) propionate), 1,3,5-trimethyl-2,4,6-tris (3,5-di-tert-butyl-4-hydroxybenzyl) benzene, etc. Among these, pentaerythritol tetrakis (3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate are preferred. Commercially available products include those manufactured by ADEKA Corporation under the trade names "ADEKA STAB AO-60" and "ADEKA STAB AO-330."
[0126] The phosphite compound is preferably a compound represented by the formula: R 2 OP(OR 3 )(OR 4 ) (In the formula, R 2 , R 3 and R 4 are each a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, or an aryl group having 6 to 30 carbon atoms, and R 2 , R 3 and R 4 At least one of the groups is an aryl group having 6 to 30 carbon atoms.) Examples of the compound include compounds represented by the following formula: Examples of the phosphite compound include triphenyl phosphite, tris(nonylphenyl)phosphite, dilauryl hydrogen phosphite, triethyl phosphite, tridecyl phosphite, tris(2-ethylhexyl)phosphite, tris(tridecyl)phosphite, tristearyl phosphite, diphenyl monodecyl phosphite, monophenyl didecyl phosphite, diphenyl mono(tridecyl)phosphite, tetraphenyl dipropylene glycol diphosphite, tetraphenyl tetra(tridecyl)pentaerythritol tetraphosphite, hydrogenated bisphenol A phenol phosphite polymer, diphenyl hydrogen phosphite, 4,4'-butylidene-bis(3-methyl-6-tert-butylphenyl di(tridecyl)phosphite), tetra(tridecyl) 4,4'-isopropyl phosphite, tetra(tridecyl) ... propylidenediphenyl diphosphite, bis(tridecyl)pentaerythritol diphosphite, bis(nonylphenyl)pentaerythritol diphosphite, dilauryl pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, tris(4-tert-butylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, hydrogenated bisphenol A pentaerythritol phosphite polymer, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, and the like. Among these, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite is preferable. An example of a commercially available product is "ADEKA STAB PEP-36" manufactured by ADEKA Corporation.
[0127] Other examples of antioxidants include the following: JP 2021-063196 A, paragraphs 0067 to 0075; JP 2018-070722 A, paragraphs 0046 to 0057; JP 2019-056035 A, paragraphs 0030 to 0037; and WO 2017 / 038949 A, paragraphs 0066 to 0078. The contents of these are incorporated herein by reference.
[0128] The content of the antioxidant in the resin composition of the present embodiment is 0.01 parts by mass or more, preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.3 parts by mass or more, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the polycarbonate resin. By making it equal to or more than the lower limit, the effect of suppressing thermal deterioration and oxidative deterioration of the resin during melt kneading, molding, and use as a molded body tends to be improved, and discoloration of the resin tends to be more effectively suppressed. In addition, the upper limit of the content of the antioxidant is preferably 2.0 parts by mass or less, more preferably 1.5 parts by mass or less, and even more preferably 1.0 parts by mass or less, relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the polycarbonate resin. By making it equal to or less than the upper limit, adverse effects on appearance and physical properties due to aggregation of additives such as antioxidants can be effectively suppressed. The resin composition of the present embodiment may contain only one type of antioxidant, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0129] <Ultraviolet absorbing agent> The resin composition of the present embodiment may contain an ultraviolet absorber. As the ultraviolet absorber, benzotriazole-based ultraviolet absorbers, benzoxazine-based ultraviolet absorbers, triazine-based ultraviolet absorbers, and malonic acid ester-based ultraviolet absorbers are preferred, and benzotriazole-based ultraviolet absorbers are preferred. By selecting an organic ultraviolet absorber, the transparency and mechanical properties of the resin composition of the present embodiment can be improved.
[0130] Examples of the benzotriazole-based ultraviolet absorbers include 2-(2-hydroxy-5-methylphenyl)-2H-benzotriazole, 2-(2-hydroxy-3,5-di-tert-butylphenyl)-2H-benzotriazole, 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-2H-benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)-2H-benzotriazole, 2-(3,5-di-tert-octyl-2-hydroxyphenyl)-2H-benzotriazole, 2- (3,5-di-tert-amyl-2-hydroxyphenyl)-2H-benzotriazole, 2-(3-lauryl-5-methyl-2-hydroxyphenyl)-2H-benzotriazole, 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chloro-2H-benzotriazole, 2-(3-tert-butyl-5-methyl-2-hydroxyphenyl)-5-chloro-2H-benzotriazole, 2-(3,5-bis(1-methyl-1-phenylethyl)-2-hydroxyphenyl)-2H-benzotriazole, Bis(3-(2H-benzotriazol-2-yl)-2-hydroxy-5-methylphenyl)methane, bis(3-(2H-benzotriazol-2-yl)-2-hydroxy-5-(1,1,3,3-tetramethylbutyl)phenyl)methane, bis(3-(2H-benzotriazol-2-yl)-2-hydroxy-5-cumylphenyl)methane, bis(3-(2H-benzotriazol-2-yl)-2-hydroxy-5-octylphenyl)methane, 1,1-bis(3-(2H-benzotriazol-2-yl)-2-hydro 1,1-bis(3-(2H-5-chlorobenzotriazol-2-yl)-2-hydroxy-5-methylphenyl)octane, 1,2-ethanediylbis(3-(2H-benzotriazol-2-yl)-2-hydroxybenzoate), 1,12-dodecanediylbis(3-(2H-benzotriazol-2-yl)-4-hydroxybenzoate), 1,3-cyclohexanediylbis(3-(5-chloro-2H-benzotriazol-2-yl)-2-hydroxybenzoate), 1,4-Butanediylbis(3-(2H-benzotriazol-2-yl)-4-hydroxy-5-methylphenylethanoate), 3,6-dioxa-1,8-octanediylbis(3-(5-methoxy-2H-benzotriazol-2-yl)-4-hydroxyphenylethanoate), 1,6-hexanediylbis(3-(3-(2H-benzotriazol-2-yl)-4-hydroxy-5-tert-butylphenyl)propionate), p-xylenediylbis(3-(3-(2H-benzotriazol-2-yl)-4-hydroxyphenyl)propionate), bis(3-(2H-benzotriazol-2-yl)-4-hydroxytoluyl)malonate, bis(2-(3-(2H-benzotriazol-2-yl)-4-hydroxy-5-octylphenyl) ethyl) terephthalate, bis(3-(2H-benzotriazol-2-yl)-4-hydroxy-5-propyltoluyl)octadiate, 2-(2H-benzotriazol-2-yl)-6-phthalimidomethyl-4-methylphenol, 2-(2H-benzotriazol-2-yl)-6-phthalimidoethyl-4-methylphenol, 2-(2H-benzotriazol-2-yl)-6-phthalimidooctyl-4-methylphenol, 2-(2H-benzotriazol-2-yl)-6-phthalimidomethyl-4-tert-butylphenol, 2-(2H-benzotriazol-2-yl)-6-phthalimidomethyl-4-cumylphenol, 2-(2H-benzotriazol-2-yl)-4,6-bis(phthalimidomethyl)phenol, etc. are included. Among these, 2-(2-hydroxy-5-tert-octylphenyl)-2H-benzotriazole is preferred.
[0131] For information on ultraviolet absorbents, please refer to the descriptions in paragraphs 0059 to 0062 of JP 2016-216534 A and paragraphs 0069 to 0082 of JP 2018-178019 A, the contents of which are incorporated herein by reference.
[0132] In the resin composition of the present embodiment, the content of the ultraviolet absorber is preferably 0.01 to 1 part by mass relative to 100 parts by mass of the polyalkylene terephthalate resin and the polycarbonate resin in total. The content of the ultraviolet absorber is more preferably 0.03 to 0.7 parts by mass, and even more preferably 0.05 to 0.5 parts by mass relative to 100 parts by mass of the polyalkylene terephthalate resin and the polycarbonate resin in total. By adding the ultraviolet absorber in such a range, good weather resistance can be imparted to the resin composition of the present embodiment. The ultraviolet absorbing agent may be contained in one kind or in two or more kinds. When two or more kinds are contained, it is preferable that the total amount is in the above range.
[0133] <Release agent> The resin composition of the present embodiment preferably contains a release agent. As the release agent, a wide variety of known release agents can be used, and examples thereof include aliphatic carboxylic acid amides, aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, and polysiloxane-based silicone oils.
[0134] Examples of the aliphatic carboxylic acid amide include compounds obtained by a dehydration reaction between a higher aliphatic monocarboxylic acid and / or a polybasic acid and a diamine. As the higher aliphatic monocarboxylic acid, saturated aliphatic monocarboxylic acids and hydroxycarboxylic acids having 16 or more carbon atoms are preferred, and examples thereof include palmitic acid, stearic acid, behenic acid, montanic acid, and 12-hydroxystearic acid. Examples of polybasic acids include aliphatic dicarboxylic acids such as malonic acid, succinic acid, adipic acid, sebacic acid, pimelic acid, and azelaic acid; aromatic dicarboxylic acids such as phthalic acid and terephthalic acid; and alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid and cyclohexylsuccinic acid. Examples of diamines include ethylenediamine, 1,3-diaminopropane, 1,4-diaminobutane, hexamethylenediamine, metaxylylenediamine, tolylenediamine, paraxylylenediamine, phenylenediamine, and isophoronediamine. As the carboxylic acid amide compound, a compound obtained by polycondensation of stearic acid, sebacic acid, and ethylenediamine is preferred, and a compound obtained by polycondensation of 2 moles of stearic acid, 1 mole of sebacic acid, and 2 moles of ethylenediamine is more preferred. In addition to bisamide compounds obtained by reacting diamines and aliphatic carboxylic acids, such as N,N'-methylenebisstearamide and N,N'-ethylenebisstearamide, dicarboxylic acid amide compounds, such as N,N'-dioctadecylterephthalamide, can also be suitably used.
[0135] Examples of the aliphatic carboxylic acid include saturated or unsaturated aliphatic mono-, di- or tri-carboxylic acids. Here, the aliphatic carboxylic acid also includes alicyclic carboxylic acids. Among these, preferred aliphatic carboxylic acids are mono- or di-carboxylic acids having 6 to 36 carbon atoms, and more preferred are saturated aliphatic mono-carboxylic acids having 6 to 36 carbon atoms. Specific examples of such aliphatic carboxylic acids include palmitic acid, stearic acid, caproic acid, capric acid, lauric acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, melissic acid, tetralinic acid, montanic acid, adipic acid, and azelaic acid.
[0136] In the ester of an aliphatic carboxylic acid and an alcohol, the aliphatic carboxylic acid may be the same as the aliphatic carboxylic acid. On the other hand, the alcohol may be, for example, a saturated or unsaturated monohydric or polyhydric alcohol. These alcohols may have a substituent such as a fluorine atom or an aryl group. Among these, a monohydric or polyhydric saturated alcohol having 30 or less carbon atoms is preferred, and an aliphatic or alicyclic saturated monohydric alcohol or an aliphatic saturated polyhydric alcohol having 30 or less carbon atoms is more preferred. Specific examples of such alcohols include octanol, decanol, dodecanol, stearyl alcohol, behenyl alcohol, ethylene glycol, diethylene glycol, glycerin, pentaerythritol, 2,2-dihydroxyperfluoropropanol, neopentylene glycol, ditrimethylolpropane, and dipentaerythritol. Specific examples of esters of aliphatic carboxylic acids and alcohols include beeswax (a mixture mainly composed of myricyl palmitate), stearyl stearate, behenyl behenate, stearyl behenate, glycerin monopalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate, pentaerythritol tetrastearate, and esters of montanic acid and polyfunctional alcohols.
[0137] Examples of the aliphatic hydrocarbons having a number average molecular weight of 200 to 15,000 include liquid paraffin, paraffin wax, microwax, polyethylene wax, Fischer-Tropsch wax, and α-olefin oligomers having 3 to 12 carbon atoms. The aliphatic hydrocarbons herein also include alicyclic hydrocarbons. The number average molecular weight of the aliphatic hydrocarbons is preferably 5,000 or less.
[0138] Examples of polyolefin waxes include polyethylene wax, polypropylene wax, and polyethylene propylene wax, with polyethylene wax being preferred. The polyolefin wax may be unmodified or modified. Examples of modified polyolefin waxes include vinyl ester modified polyolefin wax, acid modified polyolefin wax, and oxidized polyolefin wax, and oxidized polyolefin wax is preferred. Oxidized polyolefin wax has excellent compatibility with polyalkylene terephthalate resins and tends to effectively suppress mold deposits in the resulting resin composition.
[0139] The oxidized polyolefin wax can be obtained by oxidizing the corresponding unmodified polyolefin wax. Examples of the oxidized polyethylene wax include Licowax (registered trademark) PED521, PED522, and PED121 manufactured by Clariant Chemicals; Ceridust (registered trademark) 3715, and the like. In addition to the above, commercially available polyolefin waxes can be found in paragraph 0028 of JP-A-2022-140470, the contents of which are incorporated herein by reference.
[0140] The weight average molecular weight of the polyolefin wax is preferably 800 or more, more preferably 1,000 or more, even more preferably 1,500 or more, even more preferably 2,000 or more, and even more preferably 2,500 or more. By making it equal to or greater than the lower limit, the glowing time tends to be further shortened. In addition, the weight average molecular weight of the polyolefin wax is preferably 30,000 or less, more preferably 20,000 or less, even more preferably 15,000 or less, and even more preferably 10,000 or less. By making it equal to or less than the upper limit, the flowability of the resin composition during molding tends to be further improved. The weight average molecular weight can be measured by GPC (gel permeation chromatography) using a Tosoh HLC-8320GPC EcoSEC, tetrahydrofuran as the solvent, three Shodex KF-G, KF-805L, and a KF-800D as columns, at a column temperature of 40°C and a flow rate of 1.2 mL / min, and is measured as a polystyrene equivalent value detected with a detector (UV-8320) at a detection wavelength of 254 nm. In the case where the resin composition in the present embodiment contains two or more types of polyolefin waxes, the weight average molecular weight is the weight average molecular weight of the mixture.
[0141] The dropping point of the polyolefin wax is preferably 165°C or lower, more preferably 160°C or lower, even more preferably 155°C or lower, even more preferably 150°C or lower, even more preferably 145°C or lower, even more preferably 140°C or lower, even more preferably 135°C or lower, particularly more preferably 130°C or lower, and preferably 80°C or higher, more preferably 85°C or higher, even more preferably 85°C or higher, even more preferably 90°C or higher, and even more preferably 95°C or higher. The dropping point is determined by heating a polyolefin wax until it changes from a solid to a liquid state and the temperature at which the first drop of molten material falls from a standard cup having an opening of 2.8 mm.
[0142] As for the release agent, in addition to the above, the descriptions in paragraphs 0063 to 0077 of JP 2018-070722 A and the descriptions in paragraphs 0090 to 0098 of JP 2019-123809 A can be referred to, the contents of which are incorporated herein by reference.
[0143] The resin composition of the present embodiment preferably contains 0.01 parts by mass or more of the release agent relative to 100 parts by mass of the total of the polyalkylene terephthalate resin and the polycarbonate resin, more preferably 0.1 parts by mass or more, even more preferably 0.3 parts by mass or more, even more preferably 0.5 parts by mass or more, and preferably 5 parts by mass or less, more preferably 4 parts by mass or less, even more preferably 3 parts by mass or less, even more preferably 2 parts by mass or less, and may be 1 part by mass or less. By making it equal to or more than the lower limit, the releasability of the obtained molded article tends to be further improved. Also, by making it equal to or less than the upper limit, the bleed-out of the obtained molded article can be effectively suppressed. The resin composition may contain only one type of release agent, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.
[0144] <Other ingredients> The resin composition of the present embodiment may contain other components in addition to the above-mentioned components as necessary, as long as the desired physical properties are not significantly impaired. Examples of other components include thermoplastic resins other than polyarylene terephthalate resins and polycarbonate resins, and various resin additives. The other components may be contained in one type, or in any combination and ratio of two or more types. Specific examples of the additives include nucleating agents, reactive compounds (such as epoxy compounds), antistatic agents, antifogging agents, antiblocking agents, flow improvers, plasticizers, dispersants, and antibacterial agents. In addition, the resin composition of this embodiment can be blended with the additives described in paragraphs 0047 to 0103 of WO 2021 / 241471 without departing from the spirit of the present invention, the contents of which are incorporated herein by reference. In the resin composition of the present embodiment, the total amount of the polyalkylene terephthalate resin, the polycarbonate resin, the elastomer, the flame retardant, and any other components blended as necessary is 100 mass %. In the resin composition of this embodiment, the total amount of the polyalkylene terephthalate resin, polycarbonate resin, elastomer, and flame retardant preferably accounts for 85 mass% or more of the resin composition, more preferably 90 mass% or more, even more preferably 93 mass% or more, and even more preferably 95 mass% or more. In the resin composition of the present embodiment, the total amount of the polyalkylene terephthalate resin, polycarbonate resin, elastomer, flame retardant, flame retardant assistant, anti-dripping agent, ester exchange inhibitor, non-fibrous inorganic filler, antioxidant, ultraviolet absorber, and release agent preferably accounts for 90 mass% or more of the resin composition, more preferably 95 mass% or more, even more preferably 97 mass% or more, and even more preferably 99 mass% or more.
[0145] <Physical properties of resin composition> The resin composition of the present embodiment preferably has a high recycled content (recycle ratio (mass %)). Specifically, the content of the recycled material in the resin composition is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, and even more preferably 35% by mass or more. The upper limit of the recycled material may be 100% by mass, but 50% by mass or less is practical. Furthermore, in the resin composition of this embodiment, 40 to 60 mass % of the resin component can be recycled. The recycled product contained in the resin composition of the present embodiment is preferably a post-consumer recycled (PCR) product.
[0146] The resin composition of the present embodiment preferably has a high nominal strain at break. Specifically, the resin composition is injection molded into a multipurpose test piece A1 according to JIS K7139, and the nominal breaking strain measured according to JIS K7161-1 is preferably 50% or more, more preferably 74% or more, even more preferably 80% or more, and even more preferably 90% or more. There is no particular upper limit to the nominal breaking strain, but even if it is 130% or less, the required performance is sufficiently satisfied. The high nominal breaking strain can be achieved, for example, by using recycled polycarbonate resin derived from bottles or sheets which tend to have a relatively small amount of foreign matter, by using a polycarbonate resin with a low MVR, by using a polyalkylene terephthalate resin with a high intrinsic viscosity, by blending an elastomer, etc.
[0147] The resin composition of the present embodiment preferably has a high Tc (crystallization temperature). A high Tc tends to give a molded product with excellent releasability. Also, a resin composition with excellent moldability can be obtained. The Tc of the resin composition of the present embodiment, when measured according to JIS K7121, is preferably 180° C. or higher in the first cycle, more preferably 182° C. or higher, even more preferably 184° C. or higher, and even more preferably 185° C. or higher. The upper limit is preferably 200° C. or lower. The Tc of the resin composition of this embodiment, as measured according to JIS K7121, is preferably 143° C. or more in the second cycle, more preferably 150° C. or more, even more preferably 154° C. or more, and even more preferably 157° C. or more. The upper limit is preferably 190° C. or less. The high crystallization temperature can be achieved, for example, by including an ester exchange inhibitor in the resin composition, by controlling the amount of branches in the recycled polycarbonate to be equal to or less than the upper limit, by avoiding excessively high temperatures and retention during production of the resin composition, and the like.
[0148] The resin composition of the present embodiment preferably has excellent impact resistance. Specifically, the resin composition of this embodiment is injection molded into a multipurpose test piece A1 in accordance with JIS K7139, and the unnotched Charpy impact strength (unit: kJ / m) measured at a temperature of 23°C in accordance with JIS K7111-1 is 2 ) is 21kJ / m 2 It is preferable that the concentration is 25 kJ / m or more. 2 More preferably, it is 30 kJ / m or more. 2 More preferably, it is 35 kJ / m or more. 2 More preferably, it is 40 kJ / m or more. 2 More preferably, it is 45 kJ / m or more. 2 It is even more preferable that the value is equal to or greater than 50 kJ / m 2 More preferably, it is 55 kJ / m or more. 2 More particularly, the upper limit of the unnotched Charpy impact strength is, for example, 80 kJ / m 2 The following is practical. The impact resistance can be achieved, for example, by increasing the proportion of polycarbonate resin in the resin composition, using recycled polycarbonate resin with a low MVR, blending an elastomer, blending titanium oxide, etc. In particular, the resin composition of the present embodiment is highly valuable in that it can achieve excellent impact resistance despite the incorporation of a flame retardant.
[0149] The resin composition of the present embodiment preferably has excellent flame retardancy. Specifically, it is preferable that the resin composition is molded into a 1.0 mm thick test piece for the UL-94 test, and that the flame retardancy according to the UL-94 test satisfies V-0. The flame retardancy can be achieved by blending, for example, titanium oxide in addition to blending a flame retardant, a flame retardant assistant, an anti-dripping agent, and the like.
[0150] The resin composition of the present embodiment preferably has excellent tracking resistance. Specifically, the resin composition is injection molded to a size of 100 mm × 100 mm × 3 mm thickness, and the CTI value measured according to UL746A is preferably at least 600 V. There is no particular upper limit to the CTI, but even if it is 1000 V or less, the required performance is sufficiently satisfied. The tracking resistance can be achieved, for example, by blending an optimal type and amount of elastomer, optimizing the blending ratio of polycarbonate resin and polyalkylene terephthalate resin, blending titanium oxide, blending an optimal type and amount of flame retardant, etc.
[0151] The resin composition of the present embodiment can reduce the peak pressure during molding. Specifically, the peak pressure during molding when the resin composition of this embodiment is molded into a multipurpose test piece A1 according to JIS K7139 can be 102 MPa or less, 96 MPa or less, or 95 MPa or less. The lower limit of the peak pressure during molding is, for example, 40 MPa or more. The low peak pressure during molding can be achieved, for example, by using a polycarbonate resin having a low MVR value, optimizing the type and amount of elastomer, and the like. The recyclability is calculated according to the description in the Examples below. The nominal fracture strain, Tc (crystallization temperature), impact resistance, flame retardancy, tracking resistance, and peak pressure during molding are measured according to the description in the Examples below.
[0152] <Method of producing resin composition> The resin composition of this embodiment can be produced by a conventional method for producing a resin composition containing a thermoplastic resin. For example, the resin composition of this embodiment is produced by a method including feeding a polyalkylene terephthalate resin, a polycarbonate resin, a flame retardant, and other components to be mixed as necessary into an extruder and melt-kneading them. The reinforcing filler may be side-fed into the extruder. In addition, when the resin composition contains a colorant, it may be mixed with a thermoplastic resin in advance as a master batch and then melt-kneaded. The heating temperature during melt kneading can usually be appropriately selected from the range of 220 to 350°C, preferably from 220 to 320°C, and more preferably from 220 to 280°C.
[0153] <Method of manufacturing molded products> The resin composition of the present embodiment is molded according to a known method. The manufacturing method of the molded product is not particularly limited, and any molding method generally used for resin compositions can be used. Examples of such molding methods include injection molding, ultra-high speed injection molding, injection compression molding, two-color molding, gas-assisted hollow molding, molding using a heat-insulating mold, molding using a rapid heating mold, foam molding (including supercritical fluid), insert molding, IMC (in-mold coating molding), extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, press molding, blow molding, etc., and among these, injection molding is preferred. For details of the injection molding method, refer to paragraphs 0113 to 0116 of Japanese Patent No. 6183822, the contents of which are incorporated herein by reference. The mold temperature during molding such as injection molding is preferably 40 to 150°C.
[0154] <Application> An example of the resin composition of this embodiment is a pellet. The molded article of the present embodiment is formed from the resin composition of the present embodiment or the pellets of the present embodiment. The molded article of this embodiment can be used in a variety of applications, such as various storage containers, electrical and electronic equipment parts, office automation (OA) equipment parts, home appliance parts, machine mechanism parts, and vehicle parts (vehicle mechanism parts, vehicle housing parts). Vehicle parts include lamp housings, reflectors, bezels, extensions, connectors, ECU cases, head-up display housings, housings for in-vehicle cameras and millimeter-wave radars, battery cases, inverters, high-voltage connectors, sensor housings, and housings for charging components for EVs. Examples of electric and electronic components include display devices such as personal computers, game consoles and televisions, printers, copy machines, scanners, fax machines, electronic organizers and PDAs, electronic desk calculators, electronic dictionaries, cameras, video cameras, mobile phones, battery packs, drives and readers for recording media, mice, numeric keypads, CD players, MD players, portable radios and audio players, housings, covers, keyboards, buttons, switch components, power meter cases, battery cases, battery transport trays, relays, sensors, actuators, terminal switches and grill cooking appliance parts. EXAMPLES
[0155] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or the like, measurements can be made using other instruments with equivalent performance.
[0156] 1.Raw materials The raw materials shown in Tables 1 and 2 below were used.
[0157] [Table 1]
[0158] [Table 2]
[0159] <Measurement of the amount of bisphenol A (BPA) in polycarbonate resin (virgin and recycled products)> Polycarbonate resin was dissolved in dichloromethane solution, methanol was dropped therein to reprecipitate the polymer component, filtered, and the filtrate was dried and dissolved in 5 mL of methanol. The methanol solution was analyzed by high performance liquid chromatography (Shimadzu Corporation "LC-20AD Prominence") to determine the content of bisphenol A. A calibration curve prepared from a separately prepared standard substance was used to calculate the content.
[0160] <Measurement of branching amount of polycarbonate resin (virgin and recycled products)> In this embodiment, the branching amount of the polycarbonate resin means the total content (unit: mass ppm) of PSA, PSA-Me, PBA, and dicarboxylic acid (DA1, DA2) (structures shown below) obtained after hydrolysis of the polycarbonate resin. Specifically, 0.5 g of polycarbonate resin was dissolved in 5 mL of methylene chloride, and then 45 mL of methanol and 5 mL of 25% by mass aqueous sodium hydroxide solution were added, and the mixture was stirred for 30 minutes at 70° C. to hydrolyze (methylene chloride solution). Then, 6N hydrochloric acid was added to the methylene chloride solution to adjust the pH of the solution to about 2, and the volume was adjusted to 100 mL with pure water. Next, 20 μL of the prepared methylene chloride solution was injected into a liquid chromatograph to measure the contents of PSA, PSA-Me, PBA, and dicarboxylic acids (DA1 and DBA2) whose structures are shown below, and the total amount of these was taken as the branching amount of the polycarbonate resin (unit: mass ppm). The liquid chromatography and measurement conditions are as follows. Liquid chromatography: Shimadzu Corporation LC-10AD Column: YMC PACK ODS-AM M-307-3 4.6mm ID x 75mm L Detector: UV280nm Eluent: (A) 0.05% trifluoroacetic acid aqueous solution (B) methanol Gradient conditions: 0 min (B=40%), 25 min (B-95%) The contents of PSA, PSA-Me, PBA, PBA dicarboxylic acid, and Pxt were calculated from their respective peak areas based on a calibration curve prepared with bisphenol A.
[0161] The above PSA, PSA-Me, PBA, and dicarboxylic acid (DA1, DA2) are as follows. [ka]
[0162] <Measurement of MVR of polycarbonate resin (virgin and recycled products)> The melt volume rate of polycarbonate resin (virgin and recycled products) was measured in accordance with ISO1133 at 300℃ and a load of 1.20kgf. The unit is cm 3 / 10min.
[0163] <Dispersion ratio (Mw / Mn) of polycarbonate resin (virgin and recycled products)> The weight average molecular weight (Mw) and number average molecular weight (Mn) of polycarbonate resin (virgin and recycled products) were measured using HLC-8320GPC / EcoSEC (TOSOH Corporation) and calculated in terms of polystyrene. The measurement conditions are as follows. Column: Shodex KF-G + KF-805L x 3 + KF-800D Detector: UV detector 254nm Column temperature: 40℃ Eluent: tetrahydrofuran (THF) Based on the obtained Mw and Mn, the dispersity (Mw / Mn) was calculated. In this specification, Mw and Mn for all components are values measured by the above-mentioned method. In addition, when two or more kinds of polycarbonate resins are contained, the Mw and Mn of the polycarbonate resins are the Mw and Mn of the mixture, respectively. The same applies to the other components.
[0164] <Measurement of the amount of metal elements> Qualitative / semi-quantitative analysis of metal elements (Al, Fe, P) in polycarbonate resin was performed by ICP emission spectrometry. In this case, 200 mg of sample was weighed out as pretreatment, and Kjeldahl wet decomposition (sulfuric acid / nitric acid, sulfuric acid / hydrogen peroxide) was performed, and the volume was adjusted to 50 mL. Then, ICP emission spectrometry was performed by acid concentration matching single point calibration method. The unit is shown in ppm by mass. ICP emission analysis was performed using a ThermoThromo Fisher Scientific "iCAP7600duoiCAP76000uo" by axial / radial photometry.
[0165] Details of the above PC-1 to PC-4 are as follows.
[0166] [Table 3] *ND: Below detection limit
[0167] 2. Examples 1 to 3, Comparative Examples 1 and 2 <Compound> The components shown in Table 1 or Table 2 were mixed uniformly in the ratios shown in Table 4 (each component in Table 4 is shown in parts by mass) using a tumbler mixer. The resulting mixture was fed to a twin-screw extruder ("TEX30α" manufactured by The Japan Steel Works, Ltd.). The resin composition was melt-kneaded under conditions of a cylinder set temperature of 260°C and a screw rotation speed of 200 rpm, and was quenched in a water tank and pelletized using a pelletizer to obtain pellets of the resin composition.
[0168] <Recycled ratio (mass%)> The proportion (mass %) of the recycled components relative to the total amount of the resin composition was calculated.
[0169] <Destructive strain> The resin composition pellets obtained above were dried at 120°C for 5 hours, and then injection molded into JIS K7139 multipurpose test pieces A1 (4 mm thick) using an injection molding machine "J-85AD-60H" manufactured by Japan Steel Works, Ltd., under conditions of a cylinder temperature of 250°C and a mold temperature of 80°C. The nominal tensile strain at break was determined based on JIS K7161-1.
[0170] <Crystallization temperature (Tc)> The pellets of the resin composition were measured using a differential scanning calorimeter (DSC) based on JIS K7121. The temperature was raised from 40°C to 300°C at a heating rate of 20°C / min under a nitrogen atmosphere, and then the temperature was held at 300°C for 3 minutes, and then the temperature was lowered to 40°C at a heating rate of -20°C / min. This constituted one cycle, and two cycles were performed. The maximum peak temperature due to crystallization during the temperature drop in each cycle was taken as the crystallization temperature. The differential scanning calorimeter used was "DSC7020" manufactured by Hitachi High-Tech Science Corporation.
[0171] <Notched Charpy impact strength> The resin composition pellets obtained above were dried at 120°C for 5 hours, and then injection molded into JIS K7139 multipurpose test pieces A1 (4 mm thick) using an injection molding machine "J-85AD-60H" manufactured by Japan Steel Works, Ltd., under conditions of a cylinder temperature of 250°C and a mold temperature of 80°C. Using the above multipurpose test piece (4 mm thick), the unnotched Charpy impact strength (unit: KJ / m 2 ) was measured.
[0172] <Flame retardancy> The resin composition pellets obtained above were dried at 120°C for 5 hours, and then injection molded into combustion test specimens (12.7 mm width x 127 mm length x 1.1 mm thickness) using an injection molding machine (Japan Steel Works, Ltd., "J-50AD") under conditions of a cylinder temperature of 250°C and a mold temperature of 80°C. The obtained combustion test specimens were left to stand in an atmosphere of 70°C for one week, and then the flame retardancy was evaluated according to the Underwriters Laboratories Subject 94 (UL94) method.
[0173] <Tracking resistance (CTI)> The pellets obtained above were dried at 120°C for 6 hours until just before use, and then a flat test piece measuring 100 mm x 100 mm x 3 mm was molded using an injection molding machine (Nissei Plastic Industrial Co., Ltd. "NEX-80") at a cylinder temperature of 260°C to perform a tracking resistance test as specified in the test method UL746A23, and measured in accordance with ASTM D3638. An electrolyte (aqueous solution of 0.1% ammonium chloride, resistivity 385 Ω·cm at 23°C) was dropped from the nozzle of the device at 30 second intervals, and a voltage of 600 V or less (in 25 V steps) was applied between both platinum electrodes to measure the number of electrolyte drops until tracking occurred, and the maximum voltage (unit: V) at which the average value of 5 drops was 50 drops was determined.
[0174] <Peak pressure during molding (MPa)> The resin composition pellets obtained above were dried at 120°C for 5 hours, and then the peak injection pressure (MPa) was read when injection molding JIS K7139 multipurpose test piece A1 (4 mm thick) using an injection molding machine "J-85AD-60H" manufactured by Japan Steel Works, Ltd. under conditions of a cylinder temperature of 250°C and a mold temperature of 80°C.
[0175] [Table 4]
[0176] As is clear from the above results, the resin composition of the present invention was excellent in various physical properties with good balance.
Claims
1. For a total of 100 parts by mass of polyalkylene terephthalate resin and polycarbonate resin, Contains 3 to 30 parts by mass of elastomer, Contains 5 to 50 parts by mass of a flame retardant, a mass ratio of the polyalkylene terephthalate resin to the polycarbonate resin in a total of 100 parts by mass of the polyalkylene terephthalate resin and the polycarbonate resin is 80 / 20 to 20 / 80; The polycarbonate resin contains recycled polycarbonate resin, The melt volume rate (MVR) of recycled polycarbonate resin measured according to ISO 1133 at 300°C and a load of 1.20 kgf is 2 to 11 cm 3 / 10 minutes, and the branching amount is 50 to 3500 ppm by mass; Resin composition.
2. The mass ratio of the polyalkylene terephthalate resin to the polycarbonate resin in a total of 100 parts by mass of the polyalkylene terephthalate resin and the polycarbonate resin is 30 / 70 to 55 / 45. The resin composition according to claim 1.
3. The resin composition according to claim 1 or 2, wherein the recycled polycarbonate resin comprises a polycarbonate resin derived from a bottle and / or a sheet.
4. The resin composition according to claim 1 or 2, further comprising an ester exchange inhibitor in an amount of 0.01 to 2 parts by mass per 100 parts by mass of the polyalkylene terephthalate resin and the polycarbonate resin combined.
5. The resin composition according to claim 1 or 2, wherein the polyalkylene terephthalate resin comprises a polybutylene terephthalate resin.
6. a mass ratio of the polyalkylene terephthalate resin to the polycarbonate resin in a total of 100 parts by mass of the polyalkylene terephthalate resin and the polycarbonate resin is 30 / 70 to 55 / 45; The recycled polycarbonate resin comprises a polycarbonate resin derived from a bottle and / or a sheet, Further, the composition contains an ester exchange inhibitor in an amount of 0.01 to 2 parts by mass per 100 parts by mass of the polyalkylene terephthalate resin and the polycarbonate resin in total, the polyalkylene terephthalate resin comprises a polybutylene terephthalate resin, The resin composition according to claim 1.
7. A pellet of the resin composition according to claim 1, 2 or 6.
8. A molded article formed from the resin composition according to claim 1, 2 or 6.
9. A molded article formed from the pellets of claim 7.
Citation Information
Patent Citations
Heat resistant aromatic polycarbonate - polyester composition
WO2021186025A1